Laminated Sheet
The laminated sheet with specific film configurations addresses the issue of 'yuzu skin' and optical distortion in adhesive layers, ensuring high smoothness and optical homogeneity for use in display devices.
Patent Information
- Application Number
- JP2020159304
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-24
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-09-24
AI Technical Summary
Existing adhesive sheets used in display devices face challenges with the occurrence of 'yuzu skin' on the adhesive layer, which affects optical homogeneity due to high-definition displays, and current solutions fail to adequately address this issue.
A laminated sheet configuration with a first and second film, where the film surfaces in contact with the adhesive layer have a maximum height of less than 50 nm and a total thickness of 80 μm or more, ensuring high smoothness and suppressing optical distortion.
The laminated sheet achieves excellent optical homogeneity by preventing the occurrence of 'yuzu skin' and optical distortion, making it suitable for use in optical components.
Smart Images

Figure 0007624817000003 
Figure 0007624817000004 
Figure 0007624817000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated sheet. [Background technology]
[0002] Generally, adhesives (also called pressure-sensitive adhesives; the same applies below) are in a soft solid (viscoelastic) state in a temperature range around room temperature, and have the property of easily adhering to an adherend when pressure is applied. Taking advantage of such properties, adhesives are typically in the form of adhesive sheets containing a layer of the adhesive, and are widely used in various industrial fields, from home appliances to automobiles and office automation equipment. Patent Document 1 is an example of a technical document related to adhesive sheets. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6300788 Summary of the Invention [Problem to be solved by the invention]
[0004] From the viewpoints of productivity, handling, convenience of storage and transportation, etc., it is desirable for the adhesive sheet to be rolled up into a roll shape. In addition, since the adhesive sheet before use (i.e., before being attached to an adherend) may be processed, stored, distributed, etc. in the form of a laminated sheet laminated with a release liner that protects the adhesive surface of the adhesive sheet, it is desirable for the laminated sheet to also be in the form of a roll. Patent Document 1 relates to a double-sided adhesive sheet that is wound up and stored in a roll, and proposes using a release film that is attached to the first surface of the adhesive layer and a release film that is attached to the second surface of the adhesive layer, the surface opposite to the surface that contacts the adhesive layer being highly smooth, in order to prevent the occurrence of a phenomenon in which multiple minute irregularities (citrus peel) occur on the surface of the adhesive layer.
[0005] However, due to the recent trend towards higher resolution displays in display devices, there is a tendency for the demand for optical homogeneity in the pressure-sensitive adhesive layer to become more sophisticated, and it is becoming increasingly difficult to adequately meet the above demands by simply focusing on preventing the occurrence of citrus peel on the surface of the pressure-sensitive adhesive layer.
[0006] Therefore, an object of the present invention is to provide a laminate sheet including a pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer having excellent optical homogeneity. [Means for solving the problem]
[0007] According to this specification, a laminate sheet is provided that includes a pressure-sensitive adhesive layer, a first film laminated on a first surface of the pressure-sensitive adhesive layer, and a second film laminated on a second surface of the pressure-sensitive adhesive layer. The first film is a release film whose surface A, which is the surface that contacts the pressure-sensitive adhesive layer, is a release surface. The first film has a maximum peak height Rp 1A The laminate sheet has a total thickness T of the first film and the second film. SUM is 80 μm or more.
[0008] In the laminate sheet having such a configuration, the first surface of the pressure-sensitive adhesive layer (hereinafter also referred to as the "first adhesive surface") has a thickness of Rp 1A By contacting the release surface with a thickness of <50 nm, a high degree of smoothness can be achieved on the first adhesive surface. SUM By setting the thickness of the first adhesive surface to 80 μm or more, the occurrence of optical distortion in the pressure-sensitive adhesive layer can be suitably suppressed. By providing the first adhesive surface with high smoothness and suppressing the occurrence of optical distortion, a laminate sheet having a pressure-sensitive adhesive layer with excellent optical homogeneity can be realized. In this specification, the adhesive surface refers to the surface of the adhesive layer on which the release film is laminated in the laminate sheet, that is, the surface which can be attached to an adherend by peeling off the release film.
[0009] The laminate sheet disclosed herein can be preferably implemented in an embodiment in which the adhesive layer is an adhesive layer formed from a photocurable adhesive composition. The photocurable adhesive composition is suitable for forming an adhesive layer having high surface smoothness. In an embodiment in which a photocurable adhesive composition is used to form the adhesive layer, the above-mentioned T SUM It is particularly effective to suppress the occurrence of optical distortion by adopting a configuration that satisfies the above.
[0010] In some embodiments, at least one of the first film and the second film has a relationship between a thickness T [mm] and an elastic modulus E' [MPa] of 0.10 [N mm]. <E’×T 3 It is preferable that the above-mentioned condition is satisfied. With a laminate sheet having such a configuration, the occurrence of optical distortion in the pressure-sensitive adhesive layer can be effectively suppressed.
[0011] In some embodiments of the laminate sheet disclosed herein, the laminate sheet has a shear peel strength Fs1 of the surface A of the first film relative to the first surface of the pressure-sensitive adhesive layer of 0.5 N / 4 cm 2 More than 250N / 4cm 2 A laminate sheet having a shear peel strength Fs1 in the above range can favorably exhibit the effect of suppressing the occurrence of optical distortion in the pressure-sensitive adhesive layer.
[0012] In some embodiments of the laminate sheet disclosed herein, the second film may be a release film in which side A, which is the side in contact with the pressure-sensitive adhesive layer, serves as a release surface. In such an embodiment of the laminate sheet, the first film is releasably laminated to the first side of the pressure-sensitive adhesive layer, and the second film is releasably laminated to the second side of the pressure-sensitive adhesive layer. Thus, the pressure-sensitive adhesive layer may be understood as a double-sided pressure-sensitive adhesive sheet in which both the first and second sides are adhesive surfaces. The second film has a maximum peak height Rp 2A In the laminate sheet having such a configuration, the second surface (second adhesive surface) of the pressure-sensitive adhesive layer preferably has an Rp 2A By being in contact with a release surface of <50 nm, a high degree of smoothness can be achieved at the second adhesive surface.
[0013] An acrylic adhesive can be preferably used as the adhesive constituting the adhesive layer. The acrylic adhesive can easily form a highly transparent adhesive layer. The high transparency of the adhesive layer can be an advantageous feature in, for example, optical applications.
[0014] The laminated sheet disclosed herein can be preferably used for manufacturing an optical member having the above-mentioned adhesive layer, since the optical distortion of the adhesive layer is suppressed and a highly smooth adhesive surface can be easily realized. The optical member having the above-mentioned adhesive layer (hereinafter also referred to as an adhesive-type optical member) can be preferably manufactured, for example, by a method including peeling off a release film from the laminated sheet to expose an adhesive surface, and attaching the adhesive surface to an optical member as an adherend. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a laminate sheet according to one embodiment. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing a laminate sheet according to another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] A preferred embodiment of the present invention will be described below. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general knowledge in the field. In addition, in the following drawings, components and parts having the same function may be described by using the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments described in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the product actually provided.
[0017] In this specification, the term "adhesive" refers to a material that exhibits a soft solid (viscoelastic) state at temperatures near room temperature and that has the property of easily adhering to an adherend by pressure, as described above. The adhesive referred to here is generally a material having a complex tensile modulus E * (1Hz)<10 7 dyne / cm 2 The material may be a material having the properties satisfying the above (typically, a material having the above properties at 25°C).
[0018] <Example of laminated sheet configuration> The laminated sheet disclosed herein includes a pressure-sensitive adhesive layer, a first film laminated on a first surface of the pressure-sensitive adhesive layer, and a second film laminated on a second surface of the pressure-sensitive adhesive layer. The first film is a release film. Here, the release film refers to a film whose surface to be laminated on the pressure-sensitive adhesive layer is a surface (release surface) having releasability. The second film may be a release film or a non-releasable film. The laminated sheet disclosed herein can be used as a pressure-sensitive adhesive sheet by peeling off the release film laminated on the pressure-sensitive adhesive layer to expose the adhesive surface. Therefore, the laminated sheet disclosed herein can also be understood as a pressure-sensitive adhesive sheet with a release film, which includes a pressure-sensitive adhesive sheet and a release film that protects the adhesive surface of the pressure-sensitive adhesive sheet.
[0019] FIG. 1 shows a schematic structure of a laminated sheet according to an embodiment. The laminated sheet 40 includes an adhesive layer 10, a first film 21 laminated on a first surface 10a of the adhesive layer 10, and a second film 22 laminated on a second surface 10b of the adhesive layer. The surface (A surface) 21a of the first film 21 that contacts the adhesive layer 10 is a release surface. The surface (A surface) 22a of the second film 22 that contacts the adhesive layer 10 is also a release surface. That is, in this embodiment, both the first film 21 and the second film 22 are release films. The adhesive layer 10 included in the laminated sheet 40 can be understood as a double-sided adhesive sheet (substrate-less double-sided adhesive sheet) 42 in which the first surface 10a and the second surface 10b can be used as adhesive surfaces. "10(42)" in FIG. 1 indicates that the adhesive layer 10 can also be understood as an adhesive sheet 42 made of the adhesive layer. In the first and second films 21 and 22, the surfaces (sides B) 21b and 22b opposite to the surfaces A 21a and 22a may be either release surfaces or non-release surfaces, independently of each other. The first film 21 and the second film 22 have a total thickness T SUM The surface A 21a of the first film 21 may be selected to have a maximum peak height Rp 1A The surface A 22a of the second film 22 has a maximum peak height Rp 2A The thickness is preferably less than 50 nm, and more preferably 30 nm or less. The pressure-sensitive adhesive layer 10 is, for example, a pressure-sensitive adhesive layer formed from a photocurable pressure-sensitive adhesive composition. Before use, the laminate sheet 40 may be in the form of a roll 100 wound around a core (winding core) 80, as shown in Fig. 1, for example. The laminate sheet 40 may be used by peeling off the first film 21 and the second film 22 from the pressure-sensitive adhesive layer 10 and attaching the exposed pressure-sensitive adhesive surfaces 10a, 10b to an adherend.
[0020] The structure of a laminated sheet according to another embodiment is shown in FIG. 2. This laminated sheet 50 includes an adhesive layer 10, a first film 21 laminated on a first surface 10a of the adhesive layer 10, and a second film 32 laminated on a second surface 10b of the adhesive layer. In this embodiment, the A-side 32a of the second film 32, i.e., the surface laminated on the adhesive layer 10, is a non-peeling surface (non-peeling surface). The second film, whose surface laminated on the adhesive layer is non-peeling, can be understood as a supporting substrate for the adhesive layer. The adhesive layer 10 is fixed to the A-side 32a of the second film 32, i.e., is provided without the intention of separating the adhesive layer 10 from the second film 32. On the other hand, the A-side 21a of the first film 21 is a peeling surface, as in the example shown in FIG. 1. That is, in this embodiment, the first film is a peeling film, and the second film 32 is a supporting substrate. As a result, the pressure-sensitive adhesive layer 10 included in the laminate sheet 50 is integrated with the second film (support base) 32 to form a single-sided pressure-sensitive adhesive sheet 52 in which the first surface 10a can be used as an adhesive surface. Note that in the first and second films 21, 32, the surfaces (sides B) 21b, 32b opposite the surfaces A 21a, 32a may each independently be a release surface or a non-release surface. The first film 21 and the second film 32 have a total thickness T SUM The surface A 21a of the first film 21 may be selected to have a maximum peak height Rp 1A is less than 50 nm, preferably 45 nm or less, and more preferably 40 nm or less. 2A In some preferred embodiments, the maximum peak height Rp of the A side of the support substrate is 2A may be, for example, less than 50 nm, may be 45 nm or less, or may be 40 nm or less. The laminate sheet 50 before use may be in the form of a roll 200 wound around a core 80, for example, as shown in Fig. 2. The laminate sheet 50 may be used by peeling the first film 21 from the pressure-sensitive adhesive layer 10 and attaching the exposed pressure-sensitive adhesive surface 10a to an adherend.
[0021] 1 illustrates the roll body 100 in a form in which the laminate sheet 40 is wound around the core 80, the roll body 100 may be in a form not including the core 80, that is, in a form in which the laminate sheet 40 is wound alone, that is, a so-called coreless type roll body. The same applies to the roll body 200 shown in FIG. 2.
[0022] 1 illustrates roll body 100 wound with second film 22 on the inside, but the roll body may be wound with first film 21 on the inside. Similarly, while Fig. 2 illustrates roll body 200 wound with second film (supporting substrate) 32 on the inside, the roll body may be wound with first film 21 on the inside and second film (supporting substrate) 32 on the outside.
[0023] In addition, although the pressure-sensitive adhesive layer 10 has a single-layer structure as an example in FIGS. 1 and 2, the structure of the pressure-sensitive adhesive layer 10 is not limited thereto, and may have a multi-layer structure of two or more layers. For example, the pressure-sensitive adhesive layer may be configured to include two or more sub-pressure-sensitive adhesive layers made of the same or different pressure-sensitive adhesives. In addition, the pressure-sensitive adhesive layer may be a substrate-containing pressure-sensitive adhesive layer in which a non-peeling substrate is embedded (buried) between the first surface and the second surface. As the substrate, a plastic film, paper, nonwoven fabric, etc. may be used. From the viewpoint of productivity and transparency, a pressure-sensitive adhesive layer that does not incorporate a substrate between the first surface and the second surface (substrate-less pressure-sensitive adhesive layer) is preferable, and a substrate-less single-layer pressure-sensitive adhesive layer is more preferable.
[0024] <Release film> The first film in the laminate sheet disclosed herein is a release film having a release surface at least on the side (side A) to be laminated to the pressure-sensitive adhesive layer. The second film in the laminate sheet disclosed herein may be a release film having a release surface at least on the side (side A) to be laminated to the pressure-sensitive adhesive layer, or may be a supporting substrate having a non-release surface on side A. When the second film is a release film, the second film may be a release film having the same structure as the release film used as the first film, or may be a release film having a different structure.
[0025] The maximum peak height Rp of the A side of the release film (hereinafter also referred to as the "releasable A side") is preferably less than 50 nm. This makes it easy to obtain a high degree of smoothness suitable for optical applications on the surface (adhesive surface) of the adhesive layer that releasably contacts the A side. In addition, even when the laminated sheet is wound into a roll shape, for example, it is easy to maintain the high smoothness of the adhesive surface while suppressing the occurrence of orange peel.
[0026] Here, unless otherwise specified, the maximum peak height (Rp) in this specification refers to the maximum peak height determined in accordance with JIS B 0601:2001 using a contact type surface roughness measuring device. As a contact type surface roughness measuring device, for example, a stylus type surface roughness measuring device "SV3100S4" manufactured by Mitutoyo Corporation or an equivalent product can be used. The specific measurement operation and measurement conditions can be set according to the measurement conditions described in the examples below, or so as to obtain results equivalent to or corresponding to those obtained when the measurement conditions are followed.
[0027] From the viewpoint of further improving the smoothness of the adhesive surface, the maximum peak height Rp of the peelable A side is advantageously 45 nm or less, preferably 40 nm or less, and may be 35 nm or less, or may be 30 nm or less. In some embodiments, the maximum peak height Rp of the peelable A side may be 25 nm or less, may be 20 nm or less, or may be less than 20 nm. The lower limit of the maximum peak height Rp of the peelable A side is not particularly limited. From the viewpoint of improving the smoothness of the adhesive surface, the smaller the maximum peak height Rp of the peelable A side, the more preferable. On the other hand, from the viewpoint of cost and productivity, in some embodiments, the maximum peak height Rp of the peelable A side may be, for example, 2 nm or more, 5 nm or more, 10 nm or more, 15 nm or more, or 20 nm or more. Examples of suitable embodiments of the laminate sheet disclosed herein may include embodiments in which the maximum peak height Rp of the peelable A side is 20 nm or more and less than 50 nm, 20 nm or more and less than 30 nm, 5 nm or more and less than 50 nm, 5 nm or more and less than 30 nm, 5 nm or more and less than 20 nm, etc.
[0028] In an embodiment in which both the first and second films are release films, it is preferable that at least one of the first and second films, and it is more preferable that both the first and second films, satisfy the upper limit, lower limit or numerical range of the maximum peak height Rp of any of the above-mentioned peelable side A.
[0029] In an embodiment in which both the first and second films are release films, the maximum peak height Rp of the A side of the second film 2A is the maximum peak height Rp of the A side of the first film 1A In some embodiments, Rp 1A and Rp 2A The absolute value of the difference between 1A -Rp 2A |) may be, for example, about 20 nm or less, and from the viewpoint of efficiently increasing the optical homogeneity of the pressure-sensitive adhesive layer, it is preferably about 10 nm or less, and more preferably about 5 nm or less.
[0030] The release film used as the first film and / or the second film is not particularly limited and can be appropriately selected according to purpose.Non-limiting examples of the release film that can be used include a release film having a release treatment layer on the surface of the release film substrate; a release film made of a low-adhesion resin such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin resin (polyethylene, polypropylene, etc.); etc.In some embodiments, a release film having a release treatment layer on a release film substrate can be preferably used.
[0031] As the release film substrate, various plastic films can be used. In this specification, the plastic film is typically a non-porous sheet, and is a concept that is distinguished from, for example, nonwoven fabric (i.e., does not include nonwoven fabric).
[0032] Examples of materials for the plastic film include polyester-based resins such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); polyolefin-based resins such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-butene copolymer; cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose (TAC); acetate-based resins; polycarbonate (PC); polyamides (PA) such as nylon 6, nylon 66, and partially aromatic polyamides; polyimides such as transparent polyimide (CPI); polyamideimide (PAI); polyether ether ketone (PEEK); polysulfone-based resins; polyethersulfone (PES)-based resins; cyclic polyolefins such as norbornene-based resins; (meth)acrylic resins; polyvinyl chloride-based resins; polyvinylidene chloride-based resins; polystyrene-based resins; polyvinyl alcohol (PVA)-based resins; ethylene-vinyl acetate copolymers (EVA); ethylene-vinyl alcohol copolymers; polyarylate-based resins; and polyphenylene sulfide (PSS). A release film substrate formed from any one of these resins or a mixture of two or more of them can be used. Among them, a preferred release film substrate is a polyester-based resin film (e.g., a PET film) formed from a polyester-based resin.
[0033] The release treatment layer may be formed by surface-treating the release film substrate as described above with a release treatment agent. The release treatment agent may be a known release treatment agent such as a silicone-based release treatment agent, a long-chain alkyl-based release treatment agent, a fluorine-based release treatment agent, or molybdenum (IV) sulfide. The thickness and method of forming the release treatment layer are not particularly limited, and can be set so that the desired releasability is exhibited on the A side of the release film. Although not particularly limited, the thickness of the release treatment layer is usually appropriate to be 0.01 μm or more, preferably 0.05 μm or more, and may be 0.08 μm or more. In addition, the thickness of the release treatment layer can be, for example, 3 μm or less, may be 1 μm or less, or may be 0.5 μm or less. Examples of methods for forming a release treatment layer on a release film include a method of applying a release treatment agent to a release film substrate and curing (drying, crosslinking, reacting, etc.), a method of laminating a previously prepared release treatment layer on a release film substrate, and a method of co-extrusion molding a release film substrate or its molding material and a release treatment agent, but are not limited thereto.
[0034] A preferred example of the release agent is a silicone-based release agent. The silicone-based release agent used may be in any form such as solvent-based, solventless, or water-based (aqueous solution, water dispersion). In some embodiments, solvent-based silicone-based release agents can be preferably used from the viewpoint of ease of viscosity adjustment and ease of forming a highly homogeneous release layer. The silicone-based release treatment agent may be any of addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, etc. From the viewpoint of reactivity, performance stability, etc., addition reaction type silicone-based release treatment agents can be preferably used in some embodiments.
[0035] The addition reaction type silicone release treatment agent usually contains an organohydrogenpolysiloxane and an organopolysiloxane having an aliphatic unsaturated group, and may be either a solventless type or a solvent type. For example, a heat-curable addition reaction type silicone release treatment agent that crosslinks and cures by a thermal addition reaction can be preferably used.
[0036] As the thermosetting addition reaction type silicone release agent, for example, a release agent containing a polysiloxane having a hydrogen atom (H) bonded to a silicon atom (Si) in the molecule (Si-H group-containing polysiloxane) and a polysiloxane containing a functional group (Si-H group-reactive functional group) in the molecule that is reactive to a Si-H bond (covalent bond between Si and H) (Si-H group-reactive polysiloxane) can be used. Such a release agent is cured by crosslinking caused by an addition reaction between the Si-H group and the Si-H group-reactive functional group.
[0037] In the above-mentioned Si-H group-containing polysiloxane, the Si bonded with H may be either the Si in the main chain or the Si in the side chain. The polysiloxane containing two or more Si-H groups in the molecule is preferable. The polysiloxane containing two or more Si-H groups may be a dimethylhydrogensiloxane-based polymer such as poly(dimethylsiloxane-methylsiloxane).
[0038] On the other hand, as the Si-H group reactive polysiloxane, a polysiloxane in which a Si-H group reactive functional group or a side chain containing such a functional group is bonded to Si (e.g., Si at the end of the main chain, Si inside the main chain) forming the main chain (skeleton) of the siloxane-based polymer can be used. Among them, a polysiloxane in which a Si-H group reactive functional group is directly bonded to Si in the main chain is preferred. Also, a polysiloxane containing two or more Si-H group reactive functional groups in a molecule is preferred. Examples of the Si-H group reactive functional group include alkenyl groups such as vinyl and hexenyl groups. Examples of the siloxane-based polymer forming the main chain portion include polydialkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane, and polymethylethylsiloxane (the two alkyl groups may be the same or different); polyalkylarylsiloxanes; and polymers obtained by polymerizing a plurality of Si-containing monomers, such as poly(dimethylsiloxane-methylsiloxane). A particularly preferred main chain polymer is polydimethylsiloxane.
[0039] In some embodiments, the polysiloxane containing two or more Si-H groups in the molecule and the polysiloxane containing two or more Si-H group reactive functional groups in the molecule can be preferably used as a thermosetting addition reaction type silicone release agent.The mixing ratio of the Si-H group-containing polysiloxane and the Si-H group reactive polysiloxane contained in the release agent is not particularly limited as long as the release agent is sufficiently cured and the above-mentioned silicone migration amount can be realized, but it is preferable that the mole number X of Si in the Si-H group and the mole number Y of the Si-H group reactive functional group are selected so that X≧Y, and usually X:Y is preferably about 1:1 to 2:1 (more preferably 1.2:1 to 1.6:1).
[0040] The addition reaction type silicone release agent may contain a catalyst for accelerating the crosslinking reaction. Examples of such catalysts include platinum catalysts such as platinum fine particles, chloroplatinic acid and its derivatives. The amount of catalyst added is not particularly limited, but is preferably selected from the range of 0.1 to 1000 ppm (more preferably 1 to 100 ppm) relative to the Si-H group reactive polysiloxane.
[0041] The silicone-based release treatment agent may be a mixture of the above-mentioned components prepared or obtained appropriately, or a commercially available product containing the above-mentioned components. In addition to the above-mentioned components, other known and commonly used additives such as fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, colorants (dyes, pigments, etc.) may be added as necessary.
[0042] In some other embodiments, a release film having a release treatment layer made of a long-chain alkyl release treatment agent may be preferably used. Examples of long-chain alkyl release treatment agents include polyvinyl carbamates obtained by reacting a polyvinyl alcohol polymer with a long-chain (e.g., carbon number 8 to 30) alkyl isocyanate, and alkyl urea derivatives obtained by reacting a polyethyleneimine with a long-chain (e.g., carbon number 8 to 30) alkyl isocyanate. In addition, long-chain alkyl release treatment agents containing long-chain alkyl materials as described in JP 2016-145341 A can be used as the release treatment agent for the release film used in the laminate sheet disclosed herein. The above-mentioned JP 2016-145341 A is incorporated herein by reference.
[0043] Silicone-based release treatment agents can be preferably used to prepare release films having a maximum peak height Rp of the releasable A side in the range of 20 nm or more and less than 50 nm, 20 nm or more and less than 40 nm, 20 nm or more and less than 30 nm, etc., but are not limited thereto. Non-silicone-based release treatment agents such as long-chain alkyl-based release treatment agents can be preferably used to prepare release films having a maximum peak height Rp of the releasable A side in the range of 20 nm or more and less than 50 nm, 20 nm or more and less than 40 nm, 20 nm or more and less than 30 nm, etc., and can also be preferably used to prepare release films having a maximum peak height Rp of the releasable A side in the range of 5 nm or more and less than 50 nm, 5 nm or more and less than 30 nm, 5 nm or more and less than 25 nm, 10 nm or more and less than 25 nm, 15 nm or more and less than 30 nm, 15 nm or more and less than 25 nm, etc., but are not limited thereto.
[0044] In some embodiments of the laminate sheet disclosed herein, the release film contained in the laminate sheet is preferably configured so that the residual adhesion rate of side A (release surface) measured by the following method is 60% or more (more preferably 70% or more, and even more preferably 80% or more). The residual adhesion rate of side A of the release film is typically 100% or less, and may be 95% or less, or may be 90% or less, from the practical viewpoint of cost, productivity, etc.
[0045] (Method for measuring residual adhesion rate) In an environment of 23°C and 50% RH, a product name "NO.31B" (adhesive tape with polyester base material, manufactured by Nitto Denko Corporation, width 19 mm) was laminated to a stainless steel plate by rolling a 2 kg roller back and forth once, and then left in an environment of 23°C and 50% RH for 30 minutes. After that, in the same environment, a tensile tester was used to measure the stress when the adhesive tape was peeled off 50 mm under conditions of a peel angle of 180° and a tensile speed of 300 mm / min, and the maximum stress value was read and this maximum stress value was determined as the blank peel strength (F R0 ) [N / 19mm]. In addition, in an environment of 23°C and 50% RH, a product name "NO.31B" (adhesive tape having a polyester base material, manufactured by Nitto Denko Corporation, width 19 mm) was laminated to the A side of the release film to be measured by rolling a 5 kg roller once, and this was heat-treated for 24 hours in a hot air dryer at 70°C with a load of 5 kg, and then left for 2 hours in an environment of 23°C and 50% RH. Thereafter, the adhesive tape (product name "NO.31B") was peeled off from the A side of the release film to be measured, and the adhesive tape was laminated to a stainless steel plate by rolling a 2 kg roller once, and left for 30 minutes in an environment of 23°C and 50% RH. After that, in the same environment, the stress was measured when the adhesive tape was peeled off 50 mm using a tensile tester under conditions of a peel angle of 180° and a tensile speed of 300 mm / min, and the maximum stress value at that time was read, and the maximum stress value was recorded as the residual peel strength (F R1 ) [N / 19mm]. And, the residual peel strength (F R1 ) and the peel strength of the blank (F R0 ) to calculate the residual adhesion rate [%] using the following formula. Residual adhesion rate [%]=(F R1 / F R0 ) x 100
[0046] A release film having a high residual adhesion rate tends to have good unwinding properties from a roll. This is particularly significant for a release film having a low maximum peak height Rp of the A-side (e.g., 45 nm or less, 35 nm or less, or less than 30 nm). The residual adhesion rate can be adjusted, for example, by selecting the release treatment agent used to form the release treatment layer that constitutes the A-side of the release film. When a silicone-based release treatment agent is used, it is preferable to select a non-migratory silicone-based release treatment agent.
[0047] <Support base material> In some embodiments of the laminate sheet disclosed herein, the second film may be a film in which the A-side, which is the side in contact with the pressure-sensitive adhesive layer, is non-releasable, i.e., a support substrate. As the support substrate, various plastic films can be used. The material constituting the plastic film can be arbitrarily selected from the same materials as those exemplified as the plastic films usable for the release film substrate. Among them, preferred plastic films include polyester-based resin films such as PET films, cellulose-based resin films such as diacetyl cellulose films and triacetyl cellulose (TAC) films, polyimide-based resin films such as transparent polyimide (CPI) films, and polyethersulfone (PES)-based resin films. A transparent plastic film is preferred. The A-side of the support substrate may be subjected to a surface treatment such as application of a primer, corona discharge treatment, plasma treatment, etc. Such a surface treatment can be useful for improving the adhesion between the A-side and the pressure-sensitive adhesive layer.
[0048] In the technology disclosed herein, the plastic film used as the above-mentioned support substrate or release film substrate may be any of a non-stretched film, a uniaxially stretched film, and a biaxially stretched film. The plastic film may have a single-layer structure or a multi-layer structure (e.g., a three-layer structure) including two or more sub-layers. The plastic film may contain known additives that can be used in the support substrate or release film substrate of a pressure-sensitive adhesive sheet, such as antioxidants, antiaging agents, heat stabilizers, light stabilizers, ultraviolet absorbers, colorants such as pigments and dyes, lubricants, fillers, antistatic agents, and nucleating agents. In a multi-layered plastic film, each additive may be contained in all sub-layers, or may be contained in only some of the sub-layers.
[0049] The Rp of the A-side of the supporting substrate is not particularly limited. The maximum peak height Rp of the A-side of the supporting substrate is usually appropriate to be 300 nm or less, and preferably 150 nm or less. From the viewpoint of improving the transparency of the pressure-sensitive adhesive sheet including the supporting substrate, in some embodiments, the maximum peak height Rp of the A-side of the supporting substrate is advantageously, for example, less than 50 nm, and is preferably 45 nm or less, and may be 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, or 20 nm or less. In addition, from the viewpoint of cost and productivity, in some embodiments, the maximum peak height Rp of the A-side of the supporting substrate may be, for example, 2 nm or more, 5 nm or more, 10 nm or more, or 15 nm or more. The Rp of the A-side of the supporting substrate (second film) and the Rp of the A-side of the release film (first film) may be similar or different.
[0050] <First and second film> In the laminate sheet disclosed herein, the total thickness T of the first film and the second film SUMis preferably 80 μm or more. According to this configuration, the occurrence of optical distortion in the pressure-sensitive adhesive layer can be suppressed, and the effect of improving the optical homogeneity of the pressure-sensitive adhesive layer can be exhibited. The reason for obtaining such an effect is not particularly limited, but is thought to be, for example, as follows. That is, when forming a pressure-sensitive adhesive layer from a liquid pressure-sensitive adhesive composition, shrinkage occurs due to drying or hardening, and if the degree of this shrinkage differs depending on the location, the bias (unevenness) can be observed as optical distortion of the pressure-sensitive adhesive layer. In addition, when the laminated sheet is wound into a roll shape or when the laminated sheet is unwound from the roll, the pressure-sensitive adhesive layer is subjected to elongation or shrinkage stress in its surface direction due to deformation, and the expansion and contraction of the pressure-sensitive adhesive layer due to this can also cause optical distortion of the pressure-sensitive adhesive layer. According to the laminated sheet disclosed herein, the total thickness T of the first and second films is 100 μm or more, and the thickness T of the first and second films is 100 μm or more. SUM By setting the rigidity of the laminate sheet as a whole to a certain level or higher, it is believed that by appropriately restricting the free expansion and contraction of the pressure-sensitive adhesive layer sandwiched between the first and second films, the progression of uneven expansion and contraction of the pressure-sensitive adhesive layer can be suppressed (the degree of expansion and contraction can be made uniform), and the occurrence of optical distortion can be suppressed.
[0051] In forming a pressure-sensitive adhesive layer from an active energy ray-curable pressure-sensitive adhesive composition, the curing shrinkage is generally large, and optical distortion is likely to occur due to unevenness in the curing shrinkage during the formation of the pressure-sensitive adhesive layer. SUM The effect of suppressing the occurrence of uneven stretching of the adhesive layer by being at least a certain level is particularly well exhibited in forming the adhesive layer by a method of curing a liquid film of the adhesive composition between the A-sides of the first film and the second film. Therefore, the laminate sheet disclosed herein can be particularly preferably embodied in an embodiment having an adhesive layer formed from a solventless or active energy ray-curable adhesive composition (e.g., a solventless active energy ray-curable adhesive composition).
[0052] In order to more effectively suppress the occurrence of optical distortion, in some embodiments, the total thickness T SUMis preferably 90 μm or more, more preferably 100 μm or more, may be 110 μm or more, may be 120 μm or more, or may be 140 μm or more. SUM There is no particular upper limit to the thickness T SUM is usually suitably 1000 μm or less, preferably 800 μm or less, may be 500 μm or less, may be 300 μm or less, may be 250 μm or less, may be 200 μm or less, may be 180 μm or less, or may be 160 μm or less. SUM It may also be practiced in an embodiment in which the thickness is 135 μm or less, 125 μm or less, or 115 μm or less.
[0053] The thickness of the first film is related to the thickness of the second film to a total thickness T SUM The thickness of the first film is not particularly limited and may be selected so as to be 80 μm or more. The thickness of the first film may be selected, for example, from the range of about 2 μm to 500 μm. From the viewpoint of the handleability of the first film during the production and use of the laminated sheet, the thickness of the first film is advantageously 5 μm or more, preferably 10 μm or more, and more preferably 25 μm or more. From the viewpoint of more suitably suppressing the occurrence of optical distortion of the pressure-sensitive adhesive layer, in some embodiments, the thickness of the first film is preferably 35 μm or more, more preferably 40 μm or more, and may be 45 μm or more, 50 μm or more, 60 μm or more, or 70 μm or more. Furthermore, from the viewpoint of avoiding the thickness of the laminate sheet becoming unnecessarily large, the thickness of the first film is usually suitably 300 μm or less, preferably 250 μm or less, may be 200 μm or less, may be 190 μm or less, may be 150 μm or less, may be 130 μm or less, may be 110 μm or less, may be 90 μm or less, or may be 80 μm or less.
[0054] The thickness of the second film is determined by the total thickness T SUMThe thickness of the second film is not particularly limited and may be selected so that the thickness is 80 μm or more. The thickness of the second film may be selected, for example, from the range of about 2 μm to 500 μm. From the same viewpoint as the first film, the thickness of the second film is advantageously 5 μm or more, preferably 10 μm or more, more preferably 25 μm or more, and in some embodiments, it is preferable that the thickness is 35 μm or more, more preferably 40 μm or more, and may be 45 μm or more, 50 μm or more, 60 μm or more, or 70 μm or more. In addition, the thickness of the second film is usually appropriate to be 300 μm or less, preferably 250 μm or less, may be 200 μm or less, may be 190 μm or less, may be 150 μm or less, may be 130 μm or less, may be 110 μm or less, may be 90 μm or less, or may be 80 μm or less. In some embodiments of the laminate sheet disclosed herein, from the viewpoint of suppressing optical distortion, the thicknesses of both the first and second films may be 25 μm or more (preferably both 35 μm or more, more preferably both 50 μm or more, and even more preferably both 70 μm or more). Also, from the viewpoint of avoiding an unnecessarily large thickness of the laminate sheet, in some embodiments, the thicknesses of both the first and second films may be 200 μm or less (preferably both 150 μm or less, more preferably both 150 μm or less, and even more preferably both 100 μm or less).
[0055] The thickness of the first film and the thickness of the second film may be similar or different. When the thicknesses of the first and second films are different, the relationship between their thicknesses may be first film<second film, or second film<first film.
[0056] In some embodiments of the laminate sheet disclosed herein, at least one of the first and second films (preferably both) has a relationship between the thickness T [mm] and the elastic modulus E' [MPa] as follows: 0.10 [N mm] <E’×T 3 The film may satisfy the above E' x T 3 The value of is proportional to the bending stiffness of the film. Therefore, E'×T3 A large value of means that the film has high bending rigidity. A film with higher bending rigidity can better restrict the free expansion and contraction of the PSA layer in contact with the film, thereby suppressing the occurrence of uneven expansion and contraction.
[0057] Here, the elastic modulus E' of the film can be measured using a commercially available dynamic viscoelasticity measuring device. Specifically, a test piece is prepared by cutting a sample to be measured (first film or second film) into a strip of 30 mm in length and 5 mm in width. The tensile storage modulus of this test piece is measured in the temperature range of 0°C to 100°C using a dynamic viscoelasticity measuring device (TA Instruments, RSA-III) in tensile measurement mode under the conditions of a chuck distance of 23 mm, a heating rate of 10°C / min, a frequency of 1 Hz, and a strain of 0.05%, and the obtained value is taken as the elastic modulus E' of the film.
[0058] In some embodiments, the E′×T of at least one (preferably both) of the first and second films is 3 The value of E'×T may be, for example, 0.12 N·mm or more, 0.15 N·mm or more, 0.20 N·mm or more, 0.25 N·mm or more, 0.30 N·mm or more, 0.50 N·mm or more, 0.70 N·mm or more, or 0.90 N·mm or more. 3 A pressure-sensitive adhesive sheet having a large E'×T of at least one of the first and second films (preferably both) can exhibit a better effect of suppressing the occurrence of optical distortion in the pressure-sensitive adhesive layer. 3 It is also possible to suitably implement an embodiment in which E'×T is 2.0 N·mm or more, 3.0 N·mm or more, or 4.0 N·mm or more. 3 Although there is no particular upper limit, from the viewpoint of the ease of handling of the film and the laminated sheet containing the film, it is usually appropriate that the upper limit is about 100 N·mm or less, and preferably about 50 N·mm or less (e.g., 20 N·mm or less). From the viewpoint of avoiding an unnecessarily large thickness of the laminated sheet, in some embodiments, the upper limit of E'×T 3The value of E’×T in a film with a larger 3 value may be, for example, 10 N·mm or less, 7 N·mm or less, 5 N·mm or less, or 3 N·mm or less.
[0059] The E’×T of the first film 3 and the E’×T of the second film 3 may be the same or different. The laminated sheet disclosed herein is such that the release film included in the laminated sheet (both the first and second films in the aspect where both the first and second films are release films) satisfies any of the above-described E’×T 3 and can be preferably implemented.
[0060] The elastic modulus E’ of each film is not particularly limited and may be, for example, 300 MPa or more, or 500 MPa or more. From the viewpoint of facilitating the realization of the above-described suitable E’×T 3 in some aspects, the elastic modulus E’ of the film is preferably, for example, 1000 MPa or more, and more preferably 1500 MPa or more (for example, 2000 MPa or more). The upper limit of E’ is not particularly limited. From the viewpoints of availability and ease of manufacture, the E’ of the film is usually suitably 30000 MPa or less, preferably 20000 MPa or less, and more preferably 10000 MPa or less (for example, 6000 MPa or less). The elastic modulus E’ of the film can be adjusted by the composition of the film, the materials used, their combinations, etc.
[0061] In the laminated sheet disclosed herein, the surfaces on the side opposite to the A surfaces of the first and second films (hereinafter also referred to as “B surfaces”) may each independently be release surfaces or non-release surfaces. The maximum peak height Rp of the B surface is not particularly limited. The maximum peak height Rp of the B surface may be the same as or different from the maximum peak height Rp of the A surface. In a film in which the maximum peak height Rp is different between the A surface and the B surface, the relationship of the maximum peak height Rp may be A surface < B surface or B surface < A surface.
[0062] In some embodiments, the maximum peak height Rp of side B may be, for example, less than 50 nm, 45 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 20 nm or less, or less than 20 nm. A film having a relatively small maximum peak height Rp of side B may be advantageous in terms of the productivity and availability of the film, since the maximum peak height Rp of side A and side B is not significantly different. The lower limit of the maximum peak height Rp of side B is not particularly limited, but from the viewpoint of cost and ease of production, it may be, for example, 2 nm or more, 5 nm or more, 10 nm or more, 15 nm or more, or 20 nm or more.
[0063] In some other embodiments, the maximum peak height Rp of side B may be, for example, 50 nm or more, 100 nm or more, 200 nm or more, 350 nm or more, 450 nm or more, or 550 nm or more. A film having a relatively large maximum peak height Rp of side B may be advantageous in terms of handleability due to the slipperiness of side B. There is no particular upper limit to the maximum peak height Rp of side B, but from the viewpoints of cost, availability, etc., it may be, for example, less than 2000 nm, 1500 nm or less, 1000 nm or less, 800 nm or less, 600 nm or less, 500 nm or less, or 450 nm or less.
[0064] The first and second films may both be films with a relatively small maximum peak height Rp of the B side, or may both be films with a relatively large maximum peak height Rp of the B side, or one may be a film with a relatively small maximum peak height Rp of the B side and the other may be a film with a relatively large maximum peak height Rp of the B side. The relationship between Rp of the B side of the first film and Rp of the B side of the second film is not particularly limited. The maximum peak height Rp of the B side of the second film may be similar to or different from the maximum peak height Rp of the B side of the first film. In a laminate sheet in which the maximum peak height Rp of the B side of the first film is different from that of the second film, the relationship between the maximum peak height Rp of the B side of the first and second films may be first film<second film, or second film<first film.
[0065] <Adhesive layer> In the technology disclosed herein, the type of adhesive constituting the adhesive layer contained in the laminate sheet is not particularly limited. The adhesive layer may be an adhesive layer composed of one or more adhesives selected from various known adhesives such as acrylic adhesives, rubber adhesives (natural rubber, synthetic rubber, a mixture thereof, etc.), silicone adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, and fluorine adhesives. Here, the acrylic adhesive refers to an adhesive having an acrylic polymer as the base polymer (the main component of the polymer component, i.e., a component contained in more than 50% by weight). The same applies to rubber adhesives and other adhesives. As an example of an adhesive layer that is preferable from the viewpoint of transparency, weather resistance, etc., an adhesive layer containing an acrylic adhesive in an amount of 50% by weight or more, more preferably 70% by weight or more, and even more preferably 90% by weight or more can be mentioned. The amount of the acrylic adhesive may be more than 98% by weight, and the adhesive layer may be substantially composed of an acrylic adhesive.
[0066] In this specification, "(meth)acrylic" refers collectively to acrylic and methacrylic. Similarly, "(meth)acryloyl" refers collectively to acryloyl and methacryloyl, and "(meth)acrylate" refers collectively to acrylate and methacrylate.
[0067] In this specification, the term "acrylic polymer" refers to a polymer containing a (meth)acrylic monomer as a monomer component constituting the acrylic polymer. In other words, the term refers to a polymer containing a monomer unit derived from a (meth)acrylic monomer. Here, the term "(meth)acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule.
[0068] Although not particularly limited, in one embodiment of the technology disclosed herein, the pressure-sensitive adhesive layer can be suitably prepared using a pressure-sensitive adhesive composition containing a monomer component constituting an acrylic polymer. Hereinafter, such a pressure-sensitive adhesive composition may be referred to as an "acrylic pressure-sensitive adhesive composition". Hereinafter, the "monomer component constituting an acrylic polymer" refers to a monomer component constituting an acrylic polymer in a pressure-sensitive adhesive obtained from the acrylic pressure-sensitive adhesive composition. The monomer component may be contained in the acrylic pressure-sensitive adhesive composition as an unreacted monomer (i.e., in the form of a raw material monomer in which a polymerizable functional group is unreacted), in the form of a polymer (i.e., as a monomer unit), or in both of these forms.
[0069] <Monomer component> In one embodiment of the technology disclosed herein, the pressure-sensitive adhesive layer can be formed using a pressure-sensitive adhesive composition containing the following component (A) as a monomer component constituting the acrylic polymer. In a preferred embodiment, the pressure-sensitive adhesive layer can be suitably formed using an acrylic pressure-sensitive adhesive composition containing at least the following component (A) as a monomer component constituting the acrylic polymer, and further containing the following component (B) and / or the following component (C) as necessary.
[0070] (Component (A)) The component (A) is an alkyl(meth)acrylate having an alkyl group having 2 to 18 carbon atoms at the ester end. Hereinafter, an alkyl(meth)acrylate having an alkyl group having a carbon number of X or more and Y or less at the ester end will be referred to as "C X-Y It is sometimes written as "alkyl (meth)acrylate". 2-18 C in alkyl (meth)acrylate 2-18 The structure of the alkyl group is not particularly limited, and either the alkyl group having a straight chain or a branched chain can be used. 2-18 The alkyl (meth)acrylates can be used alone or in combination of two or more.
[0071] C with a straight chain alkyl group at the ester end 2-18 Examples of alkyl (meth)acrylates include ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-undecyl (meth)acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, n-pentadecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-heptadecyl (meth)acrylate, and n-octadecyl (meth)acrylate. In addition, C 11 having a branched alkyl group at the ester end may be used. 3-18Examples of alkyl (meth)acrylates include isopropyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, isopentyl (meth)acrylate, t-pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, 2-propylheptyl (meth)acrylate, isoundecyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isomistyryl (meth)acrylate, isopentadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isoheptadecyl (meth)acrylate, and isostearyl (meth)acrylate. The technology disclosed herein is a method for producing a composition comprising the steps of: 4-9 It is preferable to use an embodiment including one or more alkyl acrylates selected from the group consisting of C. 4-9 Suitable examples of alkyl acrylates include n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate and isononyl acrylate.
[0072] ((B) component) The above-mentioned (B) component is a monomer selected from the group consisting of alicyclic monomers and heterocycle-containing monomers. This (B) component is typically used in combination with the above-mentioned (A) component, and can be useful for improving the cohesiveness, transparency, heat resistance, etc. of the pressure-sensitive adhesive.
[0073] As the alicyclic monomer, those having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having an alicyclic structure-containing group can be used without any particular limitation. The alicyclic monomer can be used alone or in combination of two or more. Here, the "alicyclic structure-containing group" refers to a portion containing at least one alicyclic structure. In addition, the "alicyclic structure" refers to a saturated or unsaturated carbon ring structure that does not have aromaticity. In this specification, the alicyclic structure-containing group may be simply referred to as the "alicyclic group". Suitable examples of the alicyclic group include a hydrocarbon group or a hydrocarbonoxy group containing an alicyclic structure.
[0074] In the technology disclosed herein, preferred examples of alicyclic monomers include alicyclic (meth)acrylates having an alicyclic group and a (meth)acryloyl group.Specific examples of alicyclic (meth)acrylates include cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and the like, as well as HPMPA, TMA-2, HCPA, and the like shown in the following chemical formula.
[0075] [ka]
[0076] The number of carbon atoms in the alicyclic group in the alicyclic monomer (in the case of an alicyclic (meth)acrylate, the portion obtained by removing the (meth)acryloyl group from the alicyclic (meth)acrylate) is not particularly limited. For example, an alicyclic monomer having an alicyclic group with 4 to 24 carbon atoms (preferably 5 to 18, more preferably 5 to 12) can be used. Among these, cyclohexyl acrylate (CHA), cyclohexyl methacrylate, isobornyl acrylate (IBXA) and isobornyl methacrylate are preferred, CHA and IBXA are more preferred, and CHA is particularly preferred.
[0077] Examples of heterocycle-containing monomers include cyclic nitrogen-containing monomers and cyclic ether group-containing monomers. Like alicyclic monomers, heterocycle-containing monomers can be useful for improving the cohesiveness, transparency, and heat resistance of the adhesive. They can also be useful for improving the adhesive strength and cohesive strength of the adhesive. The heterocycle-containing monomers can be used alone or in combination of two or more.
[0078] As the cyclic nitrogen-containing monomer, those having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having a cyclic nitrogen structure can be used without any particular limitation. The cyclic nitrogen structure is preferably one having a nitrogen atom in the cyclic structure. Examples of the cyclic nitrogen-containing monomer include lactam-based vinyl monomers such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone; oxazoline group-containing monomers such as 2-vinyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, and 2-isopropenyl-2-oxazoline; and vinyl-based monomers having nitrogen-containing heterocycles such as vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, and vinylmorpholine. Other examples of the cyclic nitrogen-containing monomer include (meth)acrylic monomers containing nitrogen-containing heterocycles such as morpholine ring, piperidine ring, pyrrolidine ring, piperazine ring, and aziridine ring. Specific examples include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylpyrrolidine, N-acryloylaziridine, etc. Among the above cyclic nitrogen-containing monomers, lactam vinyl monomers are preferred from the viewpoint of aggregation properties, etc., and N-vinylpyrrolidone is more preferred.
[0079] As the monomer having a cyclic ether group, those having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group, and having a cyclic ether group such as an epoxy group or an oxetane group can be used without any particular limitation. As the epoxy group-containing monomer, for example, glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, etc. are mentioned. As the oxetane group-containing monomer, for example, 3-oxetanylmethyl (meth)acrylate, 3-methyl-oxetanylmethyl (meth)acrylate, 3-ethyl-oxetanylmethyl (meth)acrylate, 3-butyl-oxetanylmethyl (meth)acrylate, 3-hexyl-oxetanylmethyl (meth)acrylate, etc. are mentioned.
[0080] ((C) component) The component (C) is a monomer having at least one of a hydroxy group and a carboxy group.
[0081] As the hydroxyl group-containing monomer, those having a polymerizable functional group with an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having a hydroxyl group can be used without any particular limitation. The hydroxyl group-containing monomer can be used alone or in combination of two or more. Examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; and hydroxyalkyl cycloalkane (meth)acrylates such as (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Other examples include hydroxyethyl(meth)acrylamide, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether. Among these, hydroxyalkyl(meth)acrylate is preferred. For example, hydroxyalkyl(meth)acrylate having a hydroxyalkyl group having 2 to 6 carbon atoms can be preferably used. In a preferred embodiment, one or more selected from 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate, 4-hydroxybutyl acrylate (4HBA), and 4-hydroxybutyl methacrylate can be used as the hydroxyl group-containing monomer. The hydroxyl group-containing monomer used in a preferred embodiment of the technology disclosed herein can be 4HBA alone, HEA alone, or a combination of 4HBA and HEA.
[0082] The carboxyl group-containing monomer may be any monomer having a polymerizable functional group with an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group, and having a carboxyl group, without any particular limitations. The carboxyl group-containing monomer may be used alone or in combination of two or more. Examples of the carboxyl group-containing monomer include ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, carboxyethyl (meth)acrylate, and carboxypentyl (meth)acrylate; ethylenically unsaturated dicarboxylic acids such as itaconic acid, maleic acid, fumaric acid, and citraconic acid; metal salts thereof (e.g., alkali metal salts); and anhydrides of the above ethylenically unsaturated dicarboxylic acids, such as maleic anhydride and itaconic anhydride. Among these, acrylic acid and methacrylic acid are preferred, and acrylic acid is particularly preferred.
[0083] The technology disclosed herein can be preferably implemented in an embodiment in which the (C) component contains a hydroxy group-containing monomer. That is, it is preferable that the (C) component contains only a hydroxy group-containing monomer, or contains a hydroxy group-containing monomer and a carboxy group-containing monomer. When the (C) component contains a hydroxy group-containing monomer and a carboxy group-containing monomer, the ratio of the hydroxy group-containing monomer in the entire (C) component is preferably more than about 50% by weight, and more preferably about 80% by weight or more (for example, about 90% by weight or more). It is preferable to increase the ratio of the hydroxy group-containing monomer in the (C) component from the viewpoint of reducing metal corrosion caused by carboxy groups. The technology disclosed herein can be preferably implemented in an embodiment in which the monomer component does not substantially contain a carboxy group-containing monomer. For example, the ratio of the carboxy group-containing monomer in the monomer component can be less than about 1% by weight, preferably less than about 0.5% by weight, and more preferably less than about 0.2% by weight.
[0084] The ratio of the (A) component to the entire monomer components is not particularly limited. From the viewpoint of imparting an appropriate cohesiveness to the adhesive, the ratio of the (A) component is usually about 90% by weight or less, preferably about 85% by weight or less, and more preferably about 75% by weight or less. In a preferred embodiment, the ratio of the (A) component may be about 70% by weight or less (more preferably about 60% by weight or less, further about 50% by weight or less, for example about 45% by weight or less). In addition, from the viewpoint of initial adhesion to an adherend, the ratio of the (A) component is preferably about 30% by weight or more, and more preferably about 35% by weight or more. In one embodiment, the ratio of the (A) component to the entire monomer components can be, for example, about 30 to 75% by weight.
[0085] When the monomer component includes the (B) component, the ratio of the (B) component to the entire monomer components is not particularly limited. In consideration of the balance of adhesive properties, the ratio of the (B) component is usually appropriate to be about 3% by weight or more, preferably about 5% by weight or more, more preferably about 8% by weight or more, and may be about 10% by weight or more. In addition, from the viewpoint of initial adhesion to an adherend, the ratio of the (B) component is appropriate to be about 65% by weight or less, preferably about 60% by weight or less, and more preferably about 55% by weight or less (even more preferably about 50% by weight or less, for example, less than about 50% by weight). In a preferred embodiment, the ratio of the (B) component to the entire monomer components may be about 15% by weight or more, about 20% by weight or more, about 25% by weight or more, or even about 30% by weight or more (for example, about 35% by weight or more). In one embodiment, the ratio of the (B) component to the entire monomer components may be, for example, about 20 to 50% by weight.
[0086] When the monomer component contains the (C) component, the proportion of the (C) component in the entire monomer component is not particularly limited. From the viewpoint of initial adhesion to an adherend, the proportion of the (C) component is typically about 3% by weight or more, preferably about 5% by weight or more, and more preferably about 8% by weight or more (for example, about 10% by weight or more). From the viewpoint of imparting appropriate cohesiveness to the adhesive, the proportion of the (C) component is usually preferably about 35% by weight or less, more preferably about 30% by weight or less, and even more preferably about 25% by weight or less. In one embodiment, the proportion of the (C) component can be, for example, about 15 to 30% by weight.
[0087] (Optional Monomer) The monomer components in the technology disclosed herein may contain monomers other than the above-mentioned components (A), (B) and (C) (hereinafter also referred to as "optional monomers").
[0088] Examples of the optional monomer include alkyl (meth)acrylates not belonging to the component (A), that is, alkyl (meth)acrylates in which the number of carbon atoms in the alkyl group is 1 or 19 or more (e.g., 19 to 24). Specific examples of such alkyl (meth)acrylates include methyl (meth)acrylate, n-nonadecyl (meth)acrylate, isononadecyl (meth)acrylate, n-eicosyl (meth)acrylate, isoeicosyl (meth)acrylate, etc. These can be used alone or in combination of two or more.
[0089] Other examples of the optional monomer include monomers containing functional groups other than hydroxyl and carboxyl groups. Such functional group-containing monomers can be used for the purpose of introducing crosslinking points into the acrylic polymer or increasing the cohesive strength of the acrylic polymer. Examples of functional group-containing monomers include amide group-containing monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N-methylol(meth)acrylamide; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, and 2-(meth)acrylamido-2-methylpropanesulfonic acid; phosphoric acid group-containing monomers such as 2-hydroxyethylacryloylphosphate; keto group-containing monomers such as diacetone(meth)acrylamide, diacetone(meth)acrylate, vinyl methyl ketone, and vinyl acetoacetate; isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate; alkoxy group-containing monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; and alkoxysilyl group-containing monomers such as 3-(meth)acryloxypropyltrimethoxysilane and 3-(meth)acryloxypropyltriethoxysilane. These can be used alone or in combination of two or more.
[0090] The monomer components in the technology disclosed herein may contain, as the optional monomer, a copolymerizable monomer other than the above-listed copolymerizable monomers that are copolymerizable with the above components (A), (B), and (C) for the purpose of adjusting the glass transition temperature (Tg) of the acrylic polymer, improving the cohesive strength, etc. Examples of such copolymerizable monomers include vinyl carboxylates such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene, substituted styrenes (α-methylstyrene, etc.), and vinyl toluene; aromatic ring-containing (meth)acrylates such as aryl(meth)acrylates (e.g., phenyl(meth)acrylate), aryloxyalkyl(meth)acrylates (e.g., phenoxyethyl(meth)acrylate), and arylalkyl(meth)acrylates (e.g., benzyl(meth)acrylate); olefin monomers such as ethylene, propylene, isoprene, butadiene, and isobutylene; chlorine-containing monomers such as vinyl chloride and vinylidene chloride; vinyl ether monomers such as methyl vinyl ether and ethyl vinyl ether; and macromonomers having radical polymerizable vinyl groups at the monomer ends obtained by polymerizing vinyl groups. These can be used alone or in combination of two or more.
[0091] The amount of these optional monomers used is not particularly limited and can be determined appropriately. Usually, the total amount of optional monomers used is suitably less than about 50% by weight of the monomer components, preferably about 30% by weight or less, and more preferably about 20% by weight or less. The technology disclosed herein can be preferably implemented in an embodiment in which the total amount of optional monomers used is about 10% by weight or less (for example, about 5% by weight or less) of the monomer components. When using optional monomers, from the viewpoint of appropriately exerting the effect of increasing adhesive strength and cohesive strength, the amount of the optional monomers used is suitably about 0.5% by weight or more of the monomer components, and preferably about 0.8% by weight or more. In addition, the technology disclosed herein can also be preferably implemented in an embodiment in which the optional monomers are not substantially used (for example, an embodiment in which the amount of optional monomers used is about 0.3% by weight or less, typically about 0.1% by weight or less of the monomer components).
[0092] The above-mentioned (A) component, (B) component, (C) component and optional monomer are typically monofunctional monomers. In addition to such monofunctional monomers, the above-mentioned monomer components may contain an appropriate amount of polyfunctional monomers as necessary for the purpose of adjusting the storage modulus of the adhesive layer. Here, in this specification, the monofunctional monomer refers to a monomer having only one polymerizable functional group (typically a radically polymerizable functional group) having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group. In contrast, the polyfunctional monomer refers to a monomer having at least two such polymerizable functional groups, as described later.
[0093] (Polyfunctional Monomer) The polyfunctional monomer is a monomer having at least two polymerizable functional groups (typically radically polymerizable functional groups) having an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group. Examples of polyfunctional monomers include esters of polyhydric alcohols and (meth)acrylic acid such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. Among these, preferred examples include trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Of these, preferred examples include 1,6-hexanediol diacrylate (HDDA). The polyfunctional monomers can be used alone or in combination of two or more. From the viewpoint of reactivity, etc., polyfunctional monomers having two or more acryloyl groups are usually preferred.
[0094] The amount of the polyfunctional monomer used is not particularly limited, and can be appropriately set so that the purpose of using the polyfunctional monomer is achieved. In some embodiments, the amount of the polyfunctional monomer used can be about 3% by weight or less of the monomer component, preferably about 2% by weight or less, and more preferably about 1% by weight or less (for example, about 0.7% by weight or less). The lower limit of the amount of the polyfunctional monomer used when using the monomer component is not particularly limited, as long as it is greater than 0% by weight. Usually, it is appropriate to set the amount of the polyfunctional monomer used to about 0.001% by weight or more (for example, about 0.01% by weight or more) of the monomer component, and it may be 0.05% by weight or more, or 0.1% by weight or more.
[0095] Although not particularly limited, the ratio of the total amount of the (A), (B) and (C) components to the total monomer components is typically more than about 50% by weight, preferably about 70% by weight or more, more preferably about 80% by weight or more, and even more preferably about 90% by weight or more. The technology disclosed herein can be preferably implemented in an embodiment in which the ratio of the total amount is about 95% by weight or more (e.g., about 99% by weight or more). The ratio of the total amount may be 100% by weight. The technology disclosed herein can be preferably implemented in an embodiment in which the ratio of the total amount to the total monomer components is 99.999% by weight or less (e.g., 99.99% by weight or less).
[0096] The Tg of the copolymer corresponding to the composition of the monomer components is not particularly limited and may be, for example, about -70°C or higher. If the Tg of the copolymer is high, it tends to be difficult to eliminate the optical distortion that has once occurred in the pressure-sensitive adhesive layer. For this reason, it is particularly meaningful to apply the technology disclosed herein to suppress the occurrence of optical distortion. On the other hand, a high Tg of the copolymer can be advantageous for improving the cohesiveness of the pressure-sensitive adhesive layer. In some embodiments, the Tg of the copolymer may be, for example, about -60°C or higher, preferably about -55°C or higher, more preferably about -50°C or higher, and may be about -45°C or higher. The technology disclosed herein can also be suitably implemented in an embodiment in which the Tg of the copolymer is about -40°C or higher (for example, about -35°C or higher) or even about -30°C or higher. In addition, the Tg of the copolymer is usually suitably about 0°C or lower, and is preferably about -10°C or lower from the viewpoint of the adhesiveness and low-temperature properties of the pressure-sensitive adhesive sheet. In some embodiments, the Tg of the copolymer may be about −15° C. or less, or may be about −20° C. or less. The technology disclosed herein can be preferably implemented, for example, in an embodiment in which the Tg of the copolymer is about −30° C. or more and about −10° C. or less.
[0097] Here, the Tg of a copolymer corresponding to the composition of the monomer components refers to the Tg calculated by the Fox formula based on the composition of the monomer components. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi) In the above Fox formula, Tg is the glass transition temperature of the copolymer (unit: K), Wi is the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi is the glass transition temperature of the homopolymer of monomer i (unit: K). However, in this specification, Tg is calculated taking into account only monofunctional monomers. Therefore, when the monomer component contains a polyfunctional monomer, the total amount of the monofunctional monomers contained in the monomer component is set to 100% by weight, and Tg is calculated based on the Tg of the homopolymer of each monofunctional monomer and the weight fraction of the monofunctional monomer relative to the above total amount.
[0098] The glass transition temperature of the homopolymer used to calculate Tg is a value described in a publicly known document. For example, for the monomers listed below, the following values are used as the glass transition temperatures of the homopolymers of the monomers. n-Butyl acrylate -55℃ 2-Ethylhexyl acrylate -70℃ Cyclohexyl acrylate 15℃ Isobornyl acrylate 94℃ 2-Hydroxyethyl acrylate -15℃ 4-Hydroxybutyl acrylate -40℃ N-vinylpyrrolidone 54℃ Acrylic acid 106℃ Methacrylic acid 228℃
[0099] For the glass transition temperatures of homopolymers of monomers other than those exemplified above, the values described in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989) shall be used. For monomers for which multiple values are described in this document, the highest value shall be used. For monomers for which the glass transition temperature of homopolymers is not described in the Polymer Handbook, the value obtained by the measurement method described in JP 2007-51271 A shall be used. For monomers for which the nominal value of the glass transition temperature of homopolymers is provided by the manufacturer, etc., that nominal value may be used.
[0100] <Adhesive composition> The adhesive layer in the technology disclosed herein can be formed using an adhesive composition containing the monomer components of the above-mentioned composition in the form of a polymer, an unpolymerized product (i.e., a form in which the polymerizable functional group is unreacted), or a mixture thereof. The adhesive composition can be in various forms, such as a composition containing an adhesive (adhesive component) in an organic solvent (solvent-type adhesive composition), a composition in which an adhesive is dispersed in an aqueous solvent (water-dispersed adhesive composition), a composition prepared to be cured by active energy rays such as ultraviolet rays or radiation to form an adhesive (active energy ray-curable adhesive composition), or a hot melt-type adhesive composition that is applied in a heated and molten state and forms an adhesive when cooled to around room temperature.
[0101] In this specification, the term "active energy rays" refers to energy rays having energy capable of inducing chemical reactions such as polymerization reactions, crosslinking reactions, decomposition of initiators, etc. Examples of active energy rays include light such as ultraviolet rays, visible light, and infrared rays, and radiation such as α rays, β rays, γ rays, electron beams, neutron beams, and X-rays.
[0102] The pressure-sensitive adhesive composition typically contains at least a part of the monomer components of the composition (which may be a part of the type of monomer or a part of the amount) in the form of a polymer. The polymerization method for forming the polymer is not particularly limited, and various conventionally known polymerization methods can be appropriately adopted. For example, thermal polymerization such as solution polymerization, emulsion polymerization, and bulk polymerization (typically carried out in the presence of a thermal polymerization initiator); photopolymerization carried out by irradiating light such as ultraviolet rays (typically carried out in the presence of a photopolymerization initiator); radiation polymerization carried out by irradiating radiation such as β rays and γ rays; and the like can be appropriately adopted. Among them, photopolymerization is preferable. In these polymerization methods, the mode of polymerization is not particularly limited, and the polymerization can be carried out by appropriately selecting a conventionally known monomer supply method, polymerization conditions (temperature, time, pressure, light irradiation amount, radiation irradiation amount, etc.), and materials used other than the monomer (polymerization initiator, surfactant, etc.).
[0103] In the polymerization, a known or commonly used photopolymerization initiator or thermal polymerization initiator may be used depending on the polymerization method, polymerization mode, etc. Such polymerization initiators may be used alone or in appropriate combination of two or more.
[0104] The photopolymerization initiator is not particularly limited, but examples of the photopolymerization initiator that can be used include ketal-based photopolymerization initiators, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.
[0105] Specific examples of ketal-based photopolymerization initiators include 2,2-dimethoxy-1,2-diphenylethan-1-one (for example, trade name "Irgacure 651" manufactured by BASF). Specific examples of acetophenone-based photopolymerization initiators include 1-hydroxycyclohexyl-phenyl-ketone (e.g., BASF's trade name "Irgacure 184"), 4-phenoxydichloroacetophenone, 4-t-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (e.g., BASF's trade name "Irgacure 2959"), 2-hydroxy-2-methyl-1-phenyl-propan-1-one (e.g., BASF's trade name "Darocur 1173"), methoxyacetophenone, and the like. Specific examples of the benzoin ether-based photopolymerization initiator include benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, and benzoin isobutyl ether, and substituted benzoin ethers such as anisole methyl ether. Specific examples of the acylphosphine oxide photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (e.g., BASF's trade name "Irgacure 819"), bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (e.g., BASF's trade name "Lucirin TPO"), bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and the like. Specific examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one, etc. Specific examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride, etc. Specific examples of photoactive oxime-based photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. Specific examples of benzoin-based photopolymerization initiators include benzoin, etc. Specific examples of benzyl-based photopolymerization initiators include benzyl, etc. Specific examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexyl phenyl ketone, and the like. Specific examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, and the like.
[0106] The thermal polymerization initiator is not particularly limited, and examples of the initiator that can be used include azo-based polymerization initiators, peroxide-based initiators, redox-based initiators formed by combining peroxides with reducing agents, substituted ethane-based initiators, etc. More specifically, examples of the initiator that can be used include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[N-(2-carboxyethyl)-2-methyl Examples of initiators include, but are not limited to, azo initiators such as propionamidine hydrate; persulfates such as potassium persulfate and ammonium persulfate; peroxide initiators such as benzoyl peroxide, t-butyl hydroperoxide, and hydrogen peroxide; substituted ethane initiators such as phenyl-substituted ethane; redox initiators such as a combination of a persulfate and sodium hydrogen sulfite, and a combination of a peroxide and sodium ascorbate. Thermal polymerization can be preferably carried out at a temperature of, for example, about 20 to 100°C (typically 40 to 80°C).
[0107] The amount of such a thermal polymerization initiator or photopolymerization initiator used is not particularly limited and may be a normal amount depending on the polymerization method, polymerization mode, etc. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example about 0.01 to 1 part by weight) of the polymerization initiator can be used relative to 100 parts by weight of the monomer to be polymerized.
[0108] (Adhesive composition containing polymerized and unpolymerized monomer components) A preferred embodiment of the pressure-sensitive adhesive composition includes a polymerization reaction product of a monomer mixture containing at least a part of the monomer components (raw material monomers) of the composition. Typically, the composition includes a part of the monomer components in the form of a polymer, and the remaining part in the form of an unpolymerized product (unreacted monomer). The pressure-sensitive adhesive composition including the polymerized product and the unpolymerized product of the monomer components can be preferably used, for example, as an active energy ray curable pressure-sensitive adhesive composition. The polymerization reaction product of the monomer mixture can be prepared by at least partially polymerizing the monomer mixture. The polymerization reaction product is preferably a partial polymer of the monomer mixture. Such a partial polymer is a mixture of a polymer derived from the monomer mixture and an unreacted monomer, and typically has a syrup-like appearance (viscous liquid). Hereinafter, a partial polymer having such properties may be referred to as a "monomer syrup" or simply as a "syrup."
[0109] The polymerization method for obtaining the polymerization reaction product is not particularly limited, and various polymerization methods as described above can be appropriately selected and used. From the viewpoint of efficiency and simplicity, a photopolymerization method can be preferably adopted. According to photopolymerization, the polymerization conversion rate of the monomer mixture can be easily controlled by the polymerization conditions such as the amount of light irradiation (light amount).
[0110] The polymerization conversion rate of the monomer mixture in the partially polymerized product is not particularly limited. The polymerization conversion rate can be, for example, about 70% by weight or less, and is preferably about 60% by weight or less. From the viewpoint of the ease of preparation and coatability of the adhesive composition containing the partially polymerized product, the polymerization conversion rate is usually appropriate to be about 50% by weight or less, and is preferably about 40% by weight or less (for example, about 35% by weight or less). The lower limit of the polymerization conversion rate is not particularly limited, but is typically about 1% by weight or more, and is usually appropriate to be about 5% by weight or more.
[0111] The adhesive composition containing the partial polymer of the monomer mixture can be easily obtained, for example, by partially polymerizing the monomer mixture containing all of the raw material monomers by an appropriate polymerization method (for example, photopolymerization method). The adhesive composition containing the partial polymer may contain other components (for example, photopolymerization initiator, polyfunctional monomer, crosslinking agent, acrylic oligomer described later, etc.) that are used as necessary. The method of adding such other components is not particularly limited, and for example, they may be contained in the monomer mixture in advance, or may be added to the partial polymer.
[0112] The adhesive composition disclosed herein may be in a form in which a partial polymer or a complete polymer of a monomer mixture containing some types of monomers among the monomer components (raw monomers) is dissolved in the remaining types of monomers or the partial polymers thereof. Such a form of adhesive composition is also included in the examples of adhesive compositions containing polymerized and unpolymerized monomers of the monomer components. In this specification, the term "completely polymerized" refers to a polymerization conversion rate of more than 95% by weight.
[0113] As a curing method (polymerization method) when forming an adhesive from an adhesive composition containing a polymerized product and an unpolymerized product of a monomer component, a photopolymerization method can be preferably adopted. In an adhesive composition containing a polymerization reactant prepared by a photopolymerization method, it is particularly preferable to adopt a photopolymerization method as a curing method. Since the polymerization reactant obtained by the photopolymerization method already contains a photopolymerization initiator, when the adhesive composition containing this polymerization reactant is further cured to form an adhesive, it can be photocured without adding a new photopolymerization initiator. Alternatively, the adhesive composition may be a composition in which a photopolymerization initiator is added as necessary to the polymerization reactant prepared by the photopolymerization method. The photopolymerization initiator to be added may be the same as or different from the photopolymerization initiator used in preparing the polymerization reactant. An adhesive composition prepared by a method other than photopolymerization can be made photocurable by adding a photopolymerization initiator. A photocurable adhesive composition has the advantage that even a thick adhesive layer can be easily formed. In a preferred embodiment, photopolymerization when forming an adhesive from the adhesive composition can be performed by ultraviolet irradiation. For the ultraviolet irradiation, a known high pressure mercury lamp, low pressure mercury lamp, metal halide lamp, or the like can be used.
[0114] (Adhesive composition containing monomer component in the form of a completely polymerized product) A PSA composition according to another preferred embodiment contains the monomer components of the PSA composition in the form of a complete polymer. Such a PSA composition may be in the form of, for example, a solvent-based PSA composition containing an acrylic polymer, which is a complete polymer of the monomer components, in an organic solvent, or an aqueous dispersion-based PSA composition in which the acrylic polymer is dispersed in an aqueous solvent.
[0115] (Crosslinking agent) The adhesive composition disclosed herein may contain a crosslinking agent. As the crosslinking agent, a crosslinking agent known or commonly used in the field of adhesives may be used. For example, an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, a silicone-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a silane-based crosslinking agent, an alkyl etherified melamine-based crosslinking agent, a metal chelate-based crosslinking agent, etc. may be mentioned. These may be used alone or in combination of two or more. The content of the crosslinking agent (the total amount of the crosslinking agents when two or more kinds of crosslinking agents are included) is not particularly limited. From the viewpoint of realizing a pressure-sensitive adhesive that exhibits well-balanced adhesive properties such as adhesive strength and cohesive strength, the content of the crosslinking agent is usually about 5 parts by weight or less, preferably about 0.001 to 5 parts by weight, more preferably about 0.001 to 4 parts by weight, and even more preferably about 0.001 to 3 parts by weight, relative to 100 parts by weight of the monomer components included in the pressure-sensitive adhesive composition. Alternatively, the pressure-sensitive adhesive composition may be one that does not contain the above-mentioned crosslinking agent.
[0116] (Acrylic Oligomer) The adhesive composition disclosed herein may contain an acrylic oligomer from the viewpoint of improving adhesive strength. As the acrylic oligomer, it is preferable to use a polymer having a higher Tg than the Tg of a copolymer corresponding to the composition of the monomer components (typically, the Tg roughly corresponds to the Tg of the acrylic polymer contained in the adhesive formed from the adhesive composition). By containing an acrylic oligomer, the adhesive strength of the adhesive can be improved.
[0117] The acrylic oligomer has a Tg of about 0° C. or more and about 300° C. or less, preferably about 20° C. or more and about 300° C. or less, and more preferably about 40° C. or more and about 300° C. or less. By having the Tg within the above range, the adhesive strength can be suitably improved. The Tg of the acrylic oligomer is a value calculated based on the Fox formula, like the Tg of the copolymer corresponding to the composition of the monomer components.
[0118] The weight average molecular weight (Mw) of the acrylic oligomer is typically about 1000 or more and less than about 30000, preferably about 1500 or more and less than about 20000, and more preferably about 2000 or more and less than about 10000. It is preferable that Mw is within the above range because good adhesive strength and retention properties can be obtained. The Mw of the acrylic oligomer can be measured by gel permeation chromatography (GPC) and calculated as a value equivalent to standard polystyrene. Specifically, it is measured using 2 columns of TSKgel GMH-H (20) on an HPLC 8020 manufactured by Tosoh Corporation at a flow rate of about 0.5 ml / min with tetrahydrofuran solvent.
[0119] Examples of monomers constituting acrylic oligomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, Examples of the (meth)acrylate include alkyl (meth)acrylates such as isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate; esters of (meth)acrylic acid and alicyclic alcohols such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; aryl (meth)acrylates such as phenyl (meth)acrylate and benzyl (meth)acrylate; and (meth)acrylates obtained from alcohols derived from terpene compounds. Such (meth)acrylates can be used alone or in combination of two or more.
[0120] The acrylic oligomer preferably contains an acrylic monomer having a relatively bulky structure as a monomer unit, such as an alkyl (meth)acrylate having a branched alkyl group, such as isobutyl (meth)acrylate or t-butyl (meth)acrylate; an ester of (meth)acrylic acid and an alicyclic alcohol, such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, or dicyclopentanyl (meth)acrylate; or an aryl (meth)acrylate having a cyclic structure, such as phenyl (meth)acrylate or benzyl (meth)acrylate; from the viewpoint of further improving the adhesiveness of the adhesive layer. In addition, when ultraviolet light is used during the synthesis of the acrylic oligomer or during the preparation of the adhesive layer, a saturated bond is preferable in that polymerization inhibition is unlikely to occur, and an alkyl (meth)acrylate having a branched alkyl group, or an ester with an alicyclic alcohol, can be suitably used as a monomer constituting the acrylic oligomer.
[0121] From this viewpoint, suitable examples of the acrylic oligomer include homopolymers of dicyclopentanyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), dicyclopentanyl acrylate (DCPA), 1-adamantyl methacrylate (ADMA), and 1-adamantyl acrylate (ADA), as well as copolymers of CHMA and isobutyl methacrylate (IBMA), copolymers of CHMA and IBXMA, copolymers of CHMA and acryloylmorpholine (ACMO), copolymers of CHMA and diethylacrylamide (DEAA), copolymers of ADA and methyl methacrylate (MMA), copolymers of DCPMA and IBXMA, and copolymers of DCPMA and MMA.
[0122] When the adhesive composition disclosed herein contains an acrylic oligomer, its content is not particularly limited. From the viewpoint of easily realizing the adhesive layer having the preferred storage modulus disclosed herein, the content of the acrylic oligomer is usually preferably about 20 parts by weight or less, more preferably about 15 parts by weight or less, and even more preferably about 10 parts by weight or less, relative to 100 parts by weight of the monomer component contained in the adhesive composition. The technology disclosed herein can also be preferably implemented in an embodiment that does not use an acrylic oligomer.
[0123] In addition, the adhesive composition disclosed herein can contain various additives known in the field of adhesives as necessary.For example, colorants such as dyes and pigments, antistatic agents, surfactants, plasticizers, tackifier resins, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particulate materials, foil-like materials, etc. can be appropriately added according to the application.
[0124] In the technology disclosed herein, an active energy ray curable adhesive composition (typically a photocurable adhesive composition) may be preferably used as the adhesive composition used to form the adhesive layer. From the viewpoint of environmental hygiene, the active energy ray curable adhesive composition is preferably one that does not substantially contain an organic solvent. For example, an adhesive composition having an organic solvent content of about 5% by weight or less (more preferably about 3% by weight or less, for example about 0.5% by weight or less) is preferred. In addition, a solventless adhesive composition is preferred because it is suitable for forming an adhesive layer by a method of curing a liquid film of the adhesive composition between the A-sides of a first film and a second film as described below. Here, in this specification, the solventless adhesive composition refers to an adhesive composition that does not substantially contain a solvent (meaning including organic solvents and aqueous solvents). For example, a solventless adhesive composition having a solvent content of about 5% by weight or less (more preferably about 3% by weight or less, for example about 0.5% by weight or less) is preferred. The solvent refers to a volatile component that should be removed during the formation of the adhesive layer, that is, a volatile component that is not intended to be a component of the adhesive layer that is finally formed.
[0125] <Laminated sheet> The method for producing the laminated sheet disclosed herein is not particularly limited. For example, a pressure-sensitive adhesive composition is applied to the A-side of one of the first and second films, and dried or cured to form a pressure-sensitive adhesive layer on the A-side, and the other film is laminated on the surface opposite to the A-side of the pressure-sensitive adhesive layer to obtain a laminated sheet. Alternatively, the pressure-sensitive adhesive composition sandwiched between the A-sides of the first and second films may be dried or cured to form a pressure-sensitive adhesive layer to form a laminated sheet. Various conventionally known methods can be used as a method for applying the pressure-sensitive adhesive composition. Specifically, for example, roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, extrusion coating using a die coater, etc. can be mentioned.
[0126] The laminated sheet disclosed herein can be suitably manufactured by a method including drying or curing a liquid film of a pressure-sensitive adhesive composition on the release surface of a release film to form a pressure-sensitive adhesive layer. According to this method, the pressure-sensitive adhesive composition (liquid film) in a fluid state is dried or cured in contact with the release surface, so that the smoothness of the surface of the pressure-sensitive adhesive layer formed in contact with the release surface can be precisely controlled. As the release film, one of the first film and the second film, in which the A side is the release surface, can be used. The release surface is typically a surface with a maximum peak height (Rp) of less than 50 nm. By using a release film having such a highly smooth release surface, a highly smooth adhesive surface can be stably (reproducibly) manufactured.
[0127] The laminated sheet disclosed herein can be preferably manufactured by a method including curing the liquid film of the pressure-sensitive adhesive composition between the A-sides of the first and second films to form a pressure-sensitive adhesive layer. As a method for disposing the liquid film of the pressure-sensitive adhesive composition between the A-sides of the first and second films, a method can be adopted in which the liquid pressure-sensitive adhesive composition is applied to the A-side of one film, and then the liquid film of the pressure-sensitive adhesive composition is covered with the other film. As another method, a method can be mentioned in which the first film and the second film are supplied between a pair of rolls with the A-sides facing each other, and the liquid pressure-sensitive adhesive composition is supplied between the A-sides. The pressure-sensitive adhesive composition is preferably applied at 80° C. or less, and more preferably at 60° C. or less (for example, 40° C. or less). This suppresses roughness of the surface of the pressure-sensitive adhesive layer due to the difference in thermal expansion coefficient between the first and second films and the pressure-sensitive adhesive layer, and a more smooth adhesive surface can be formed.
[0128] The thickness of the adhesive layer is not particularly limited. The thickness of the adhesive layer may be, for example, about 1 μm to 1000 μm, and is usually appropriate to be about 5 μm to 250 μm. In some embodiments, the thickness of the adhesive layer may be, for example, 10 μm or more, preferably 20 μm or more, more preferably 25 μm or more, and may be more than 25 μm. When the thickness of the adhesive layer is increased, the stress dispersion ability of the adhesive layer tends to increase. This can advantageously contribute to reducing optical distortion. The technology disclosed herein can be preferably implemented in an embodiment in which the thickness of the adhesive layer is, for example, 30 μm or more. The thickness of the adhesive layer may be 35 μm or more, 40 μm or more, or 45 μm or more. On the other hand, when the thickness of the adhesive layer is increased, the optical path passing through the adhesive layer also becomes longer, and therefore optical distortion becomes more easily recognized. Therefore, in some embodiments, the thickness of the pressure-sensitive adhesive layer is suitably, for example, 200 μm or less, and may be 150 μm or less, 100 μm or less, or 70 μm or less.
[0129] In the technology disclosed herein, the adhesive sheet constituting the laminate sheet (including the adhesive layer and may further include a supporting substrate, but not including a release film) preferably has a haze value of 3% or less. Such an adhesive sheet can be preferably used for various applications, including applications requiring transparency. For a roll of the laminate sheet that can be used for optical applications (for example, for manufacturing optical members), it is particularly meaningful that the haze value of the adhesive sheet is 3% or less. In some embodiments, the haze value of the adhesive sheet is preferably 0 to 2.5%, more preferably 0 to 2%, and may be, for example, 0 to 1.5%, or may be 0 to 1%. The above haze value can be measured by attaching the adhesive sheet to one side of an alkali glass plate and using a haze meter. As the haze meter, MR-100 manufactured by Murakami Color Research Laboratory or an equivalent product can be used. In the measurement, the alkali glass plate to which the adhesive sheet is attached is arranged so that the adhesive sheet faces the light source side. When the alkali glass itself has a haze value, the haze value of the adhesive sheet is determined by subtracting the haze value of the alkali glass plate itself from the measured value. As the alkaline glass plate, for example, slide glass S1214 manufactured by Matsunami Glass Co., Ltd. can be used.
[0130] The haze value of the adhesive layer contained in the laminate sheet disclosed herein is preferably 3% or less. An adhesive sheet having such an adhesive layer (a substrate-less double-sided adhesive sheet consisting of an adhesive layer, or a single-sided adhesive sheet including an adhesive layer and a supporting substrate laminated on the second surface of the adhesive layer) can be preferably applied to various applications including optical applications. In some embodiments, the haze value of the adhesive layer is preferably 0 to 2.5%, more preferably 0 to 2%, and may be 0 to 1.5%, or may be 0 to 1%. The technology disclosed herein can be preferably implemented in an embodiment in which the haze value of the adhesive layer is 0% or more and less than 0.5% (more preferably 0% or more and 0.4% or less, for example 0% or more and 0.3% or less). The haze value of the adhesive layer can be measured in the same manner as the haze value of the adhesive sheet, except that the adhesive layer to be measured is attached to one surface of an alkali glass plate. In a laminate sheet in which both the first and second films are release films, the adhesive sheet constituting the laminate sheet is made of the adhesive layer, so that the haze value of the adhesive sheet and the haze value of the adhesive layer coincide with each other.
[0131] The width of the laminate sheet disclosed herein is typically 5 mm or more, and may be, for example, 10 mm or more, preferably 20 mm or more, more preferably 30 mm or more, 50 mm or more, 150 mm or more, 300 mm or more, or 500 mm or more. When the width of the laminate sheet is large, optical distortion caused by uneven stretching of the adhesive layer tends to occur easily. Therefore, it is particularly meaningful to suppress the optical distortion of the adhesive layer by applying the technology disclosed herein. In addition, from the viewpoint of handleability, etc., the width of the laminate sheet is usually about 5 m or less, and may be, for example, about 4 m or less, about 3 m or less, about 2 m or less, or about 1 m or less.
[0132] The total thickness of the laminate sheet disclosed herein is not particularly limited and may be, for example, about 30 μm to 1500 μm. Here, the total thickness of the laminate sheet refers to the thickness from the side B of the first film to the side B of the second film. In some embodiments, the total thickness of the laminate sheet may be, for example, 60 μm or more, 80 μm or more, 105 μm or more, 125 μm or more, or 140 μm or more. In addition, from the viewpoint of ease of forming a roll body and lengthening the laminate sheet, in some embodiments, the total thickness of the laminate sheet may be, for example, 1000 μm or less, 500 μm or less, or 300 μm or less.
[0133] The laminate sheet disclosed herein has a shear peel strength Fs1 of 0.5 N / 4 cm between the first surface of the pressure-sensitive adhesive layer and the A side of the first film. 2 More than 250N / 4cm 2 It is preferable that the shear peel strength Fs1 of the A-side of the first film is within the above range, and thus the effect of appropriately restricting the free expansion and contraction of the pressure-sensitive adhesive layer and suppressing the occurrence of optical distortion can be suitably exhibited. In some embodiments, from the viewpoint of enhancing the effect of restricting the expansion and contraction, the shear peel strength Fs1 of the A-side of the first film is 1.0 N / 4 cm or less. 2 More than 5.0N / 4cm is preferable. 2 More preferably, it is 10N / 4cm or more. 2 More than 15N / 4cm is also acceptable. 2 More than 25N / 4cm is also acceptable. 2 More than 35N / 4cm is also acceptable. 2 More than 45N / 4cm is also acceptable. 2 More than 55N / 4cm is also acceptable. 2 From the viewpoint of ease of peeling when peeling the first film from the pressure-sensitive adhesive layer during use of the laminate sheet, in some embodiments, the shear peel strength Fs1 of the A side of the first film is, for example, 200 N / 4 cm 2 may be less than 170N / 4cm 2 Less than 150N / 4cm is also acceptable. 2 Less than 100N / 4cm is also acceptable. 2 Less than 80N / 4cm is also acceptable. 2 Less than 70N / 4cm is also acceptable.2 The following may also be applicable.
[0134] In the aspect where the second film is a release film, the shear peeling force Fs2 of the A surface of the second film with respect to the second surface of the adhesive layer is 0.5 N / 4 cm from the viewpoint of suppressing the optical distortion of the adhesive layer. 2 250 N / 4 cm or more 2 It is preferably below this value. In some aspects, for the same reason as the first film, the shear peeling force Fs2 of the A surface of the second film is preferably 1.0 N / 4 cm 2 or more, more preferably 5.0 N / 4 cm 2 or more, still more preferably 10 N / 4 cm 2 or more, it may also be 15 N / 4 cm 2 or more, and for example, it may be 200 N / 4 cm 2 or less, it may be 170 N / 4 cm 2 or less, it may also be 150 N / 4 cm 2 or less, it may also be 100 N / 4 cm 2 or less, it may also be 80 N / 4 cm 2 or less, it may also be 70 N / 4 cm 2 or less.
[0135] In the aspect where the second film is a release film, the shear peeling force Fs1 [N / 4 cm 2 of the A surface of the first film is preferably set so as to satisfy Fs1 < Fs2 in relation to the shear peeling force Fs2 [N / 4 cm 2 of the A surface of the second film. By this, when attempting to peel the first film from the first surface of the adhesive layer, the phenomenon that the second surface of the adhesive layer lifts from the second film can be suppressed. In such an aspect, the shear peeling force Fs1 of the A surface of the first film is usually appropriately 170 N / 4 cm 2 or less, preferably 150 N / 4 cm 2 or less, it may also be 100 N / 4 cm 2 or less, it may also be 80 N / 4 cm 2 or less, it may also be 70 N / 4 cm 2From the viewpoint of improving the peeling operability of the first film, in some embodiments, the shear peel force Fs1 may be 55 N / 4 cm or less. 2 Less than 45N / 4cm is also acceptable. 2 Less than 35N / 4cm is also acceptable. 2 Less than 25N / 4cm is also acceptable. 2 In the above embodiment, the shear peel strength Fs2 of the A side of the second film is usually 10 N / 4 cm 2 It is appropriate that the resistance is 15N / 4cm or more. 2 More than 30N / 4cm is also acceptable. 2 More than 50N / 4cm is also acceptable. 2 More than 70N / 4cm is also acceptable. 2 More than that is fine.
[0136] In an embodiment in which the second film is a release film, the shear peel strength Fs1 [N / 4 cm 2 ] and the shear peel strength Fs2 [N / 4cm of the A side of the second film 2 ] is the following formula: 30N / 4cm 2 It is preferable to set the Fs1+Fs2 so as to satisfy the following: ≦Fs1+Fs2; This allows the effect of appropriately restricting the free expansion and contraction of the pressure-sensitive adhesive layer to be suitably exhibited to suppress the occurrence of optical distortion. In some embodiments, from the viewpoint of enhancing the effect of restricting the expansion and contraction, the Fs1+Fs2 is 50N / 4cm 2 More than 70N / 4cm is preferable. 2 More preferably, it is 90N / 4cm or more. 2 More than 100N / 4cm is also acceptable. 2 The upper limit of Fs1+Fs2 is not particularly limited, but is usually 400N / 4cm 2 It is appropriate to set it at 300N / 4cm or less. 2 Less than 250N / 4cm is also acceptable. 2 The following is also fine.
[0137] In an embodiment in which the second film is a release film, the shear peel strength Fs1 [N / 4 cm 2 ] and the shear peel strength Fs2 [N / 4cm of the A side of the second film 2] can be set to satisfy the following formula: 0.1≦(Fs2-Fs1) / Fs2;. This can suppress the phenomenon in which the second surface of the pressure-sensitive adhesive layer lifts up from the second film when peeling the first film from the first surface of the pressure-sensitive adhesive layer. From the viewpoint of better suppressing such a phenomenon, in some embodiments, (Fs2-Fs1) / Fs2 may be, for example, 0.3 or more, 0.4 or more, or 0.5 or more. In addition, (Fs2-Fs1) / Fs2 is usually suitably set to 1.0 or less, and may be 0.95 or less, or 0.9 or less.
[0138] The shear peel strengths Fs1 and Fs2 are measured by the method described in the Examples below. The shear peel strengths Fs1 and Fs2 can be adjusted by selecting the adhesive constituting the adhesive layer (e.g., the Tg of the base polymer, the monomer composition, etc.) and the configuration of the A side of the release film to be measured (e.g., the type of release treatment agent, the thickness of the release treatment layer, etc.).
[0139] <Roll body> The matter disclosed by this specification includes a roll body including any of the laminated sheets disclosed herein in a wound form. Such a roll body typically includes a core (winding core) and a laminated sheet wound around the core. The shape of the core is not particularly limited, and may be, for example, a solid cylindrical shape, a hollow cylindrical shape (i.e., a cylindrical shape), a hollow or solid polygonal prism shape, etc. From the viewpoint of improving the handleability of the roll body, a hollow cylindrical or hollow polygonal prism-shaped core may be preferably adopted. A cylindrical core is particularly preferred.
[0140] The material constituting the core is not particularly limited, and known materials can be used. For example, paper such as cardboard, plastic materials such as PE resin, polyvinyl chloride resin, polyester, epoxy resin, phenolic resin, melamine resin, silicon resin, polyurethane, polycarbonate, acrylonitrile-butadiene-styrene copolymer resin (ABS resin), composite materials such as fiber reinforced plastic (FRP), metal materials such as iron, stainless steel (SUS), and aluminum, etc. can be mentioned.
[0141] The outer diameter of the core is not particularly limited. In some embodiments, the outer diameter of the core may be, for example, 30 mm or more, 50 mm or more, 70 mm or more, 80 mm or more, or 85 mm or more. When the outer diameter of the core is large, it tends to be easier to suppress the occurrence of orange peel on the adhesive surface and uneven expansion and contraction of the adhesive layer caused by deformation of the laminated sheet accompanying winding and unwinding. This is preferable from the viewpoint of improving the optical homogeneity of the adhesive layer. On the other hand, there is a demand to reduce the frequency of roll replacement by lengthening the laminated sheet contained in the roll body for the purpose of improving productivity, etc. In order to lengthen the laminated sheet contained in the roll body, it is advantageous to have a smaller outer diameter of the core. From this viewpoint, the outer diameter of the core is preferably, for example, 300 mm or less, and may be 250 mm or less, 200 mm or less, or 180 mm or less. The technology disclosed herein can be suitably implemented in a roll form in which the outer diameter of the core is 150 mm or less, 100 mm or less, or even 95 mm or less, and in such a form, a laminate sheet with good optical homogeneity of the pressure-sensitive adhesive layer can be realized. Note that, in the case of a winding core having a non-circular cross-sectional shape, the above-mentioned core diameter refers to the diameter of the cross-sectional shape approximating a circle.
[0142] In the case of a hollow core, the thickness of the core (i.e., the thickness of the outer wall) is not particularly limited and can be appropriately set so as to obtain a desired strength, taking into consideration the material and outer diameter of the core, etc. From the viewpoint of reducing the weight of the roll body, the thickness of the core is usually appropriate to be about 2 mm to 15 mm, and preferably about 3 mm to 10 mm.
[0143] <Application> The laminate sheet disclosed herein can have excellent optical homogeneity by suppressing the occurrence of orange peel on the adhesive surface and the occurrence of optical distortion in the adhesive layer. By utilizing such features, the laminate sheet can be preferably used, for example, for optical applications. More specifically, the laminate sheet can be preferably used for the manufacture of an optical member having an adhesive layer (adhesive-type optical member) in an embodiment in which the adhesive sheet contained in the laminate sheet is attached to an optical member. In addition, the laminate sheet can be preferably used as an adhesive-type optical member as it is or by processing the adhesive sheet contained in the laminate sheet into an appropriate size and shape in an embodiment in which the second film is a supporting substrate having a non-peeling A side and the supporting substrate is an optical member.
[0144] When an optical film is used as the optical member, the pressure-sensitive adhesive optical member is used as a pressure-sensitive adhesive optical film. As the optical film, a polarizing plate, a retardation plate, an optical compensation film, a brightness improvement film, a hard coat (HC) film, an anti-reflection film, an impact absorbing film, an antifouling film, a photochromic film, a light control film, a wavelength selective absorption film, a wavelength conversion film, and further a laminate of these can be used. The adhesive layer or adhesive sheet contained in the laminated sheet disclosed herein is also suitable for use in the ophthalmic field. The adhesive layer or adhesive sheet is not limited to the optical uses and ophthalmic uses described above, and can be applied to various uses, for example, in the form of an adhesive sheet having a general antifouling film, a heat insulating film, an impact absorbing film, etc. as a support.
[0145] The matters disclosed by this specification include the following: (1) A pressure-sensitive adhesive layer, a first film laminated on a first surface of the pressure-sensitive adhesive layer, and a second film laminated on a second surface of the pressure-sensitive adhesive layer, the first film is a release film having a release surface on side A, which is the surface in contact with the pressure-sensitive adhesive layer; The first film has a maximum peak height Rp 1A is less than 50 nm, The total thickness T of the first film and the second film SUM A laminate sheet having a thickness of 80 μm or more. (2) The laminate sheet according to (1) above, wherein the pressure-sensitive adhesive layer is an adhesive layer formed from an active energy ray-curable pressure-sensitive adhesive composition (for example, a photocurable pressure-sensitive adhesive composition). (3) At least one of the first film and the second film (preferably both) has a relationship between a thickness T [mm] and an elastic modulus E' [MPa] as follows: 0.10 [N mm] <E’×T 3 ; The laminate sheet according to (1) or (2) above, (4) The first film and the second film are each independently made of a polyester. resin film, cellulose resin film, polyimide resin film and polyethylene The laminate sheet according to any one of (1) to (3) above, selected from the group consisting of sulfone-based resin films. (5) The laminate sheet according to any one of (1) to (4) above, wherein at least one of the first film and the second film (preferably both) has a thickness of 25 μm or more (preferably 35 μm or more, more preferably 50 μm or more, and even more preferably 70 μm or more). (6) The laminate sheet according to any one of (1) to (5) above, wherein the residual adhesion rate of the side A of the first film is 60% or more. (7) A shear peel strength Fs1 of the surface A of the first film relative to the first surface of the pressure-sensitive adhesive layer is 0.5 N / 4 cm 2 More than 250N / 4cm 2 The laminate sheet according to any one of the above (1) to (6), which is: (8) The second film has a maximum peak height Rp of side A, which is the surface in contact with the pressure-sensitive adhesive layer. 2A The laminate sheet according to any one of the above (1) to (7), wherein the average particle diameter is less than 50 nm. (9) The laminate sheet according to any one of (1) to (8) above, wherein the second film is a release film having the A side as a release surface. (10) The laminate sheet according to (9) above, wherein the residual adhesion rate of the A side of the second film is 60% or more. (11) The shear peel strength Fs2 of the A side of the second film to the second side of the pressure-sensitive adhesive layer is 0.5 N / 4 cm 2 More than 250N / 4cm 2 The laminate sheet according to (9) or (10) above, which is: (12) Shear peel strength Fs1 [N / 4 cm] of the A side of the first film to the first side of the pressure-sensitive adhesive layer 2 ] and the shear peel strength Fs2 [N / 4 cm of the A side of the second film relative to the second side of the pressure-sensitive adhesive layer. 2 The laminate sheet according to any one of the above (9) to (11), wherein the relationship between Fs2 and Fs1 satisfies the following formula: 0.1≦(Fs2−Fs1) / Fs2;. (13) A laminate sheet according to any one of (1) to (12), wherein at least one of the first film and the second film has a maximum peak height Rp of 20 nm or more and less than 50 nm, 20 nm or more and 40 nm or less, or 20 nm or more and 30 nm or less on the A side, and the A side is a release treated surface with a silicone-based release treatment agent. (14) A laminate sheet according to any one of (1) to (13), wherein at least one of the first film and the second film has a maximum peak height Rp of 20 nm or more and less than 50 nm, 20 nm or more and 40 nm or less, or 20 nm or more and 30 nm or less on the A side, and the A side is a release treated surface with a long-chain alkyl release treatment agent. (15) The laminate sheet according to any one of (1) to (13), wherein at least one of the first film and the second film has a maximum peak height Rp of 5 nm or more and less than 50 nm, 5 nm or more and less than 30 nm, 5 nm or more and less than 25 nm, 10 nm or more and less than 25 nm, 15 nm or more and less than 30 nm, or 15 nm or more and less than 25 nm, and the A side is a release treated surface with a long-chain alkyl release treatment agent. (16) The laminate sheet according to any one of (1) to (15) above, wherein at least one of the first film and the second film has side A which is a release treated surface with a silicone-based release agent, and the residual adhesion rate of the release treated surface is 60% or more. (17) The laminate sheet according to any one of (1) to (16) above, wherein the pressure-sensitive adhesive layer has a substrate-less single-layer structure. (18) The haze value of the adhesive sheet excluding the release film from the laminated sheet is 3% or less. The laminate sheet according to any one of the above (1) to (17), (19) The laminate sheet according to any one of the above (1) to (18), wherein the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is an acrylic pressure-sensitive adhesive. (20) The laminate sheet according to any one of (1) to (19) above, which is used for producing an optical member having the pressure-sensitive adhesive layer. (21) The laminate sheet according to any one of (1) to (20) above, which is wound into a roll. EXAMPLES
[0146] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those specific examples. In the following description, "parts" and "%" are by weight unless otherwise specified.
[0147] <Preparation of Pressure-Sensitive Adhesive Composition> (Adhesive composition C1) 39 parts of n-butyl acrylate, 40 parts of cyclohexyl acrylate, 21 parts of 4-hydroxybutyl acrylate, 0.05 parts of 2,2-dimethoxy-1,2-diphenylethan-1-one (manufactured by IGM Resins, product name "Omnirad 651") as a photopolymerization initiator, and 0.05 parts of 1-hydroxycyclohexyl-phenyl-ketone (manufactured by IGM Resins, product name "Omnirad 184") were mixed and irradiated with ultraviolet light under a nitrogen atmosphere to prepare a partial polymer (monomer syrup). 0.5 parts of 1,6-hexanediol diacrylate was added to the obtained monomer syrup and mixed uniformly to prepare a pressure-sensitive adhesive composition C1.
[0148] (Adhesive composition C2) 70 parts of 2-ethylhexyl acrylate, 10 parts of N-vinylpyrrolidone, 20 parts of 4-hydroxybutyl acrylate, 0.05 parts of 2,2-dimethoxy-1,2-diphenylethan-1-one (manufactured by IGM Resins, product name "Omnirad 651") as a photopolymerization initiator, and 0.05 parts of 1-hydroxycyclohexyl-phenyl-ketone (manufactured by IGM Resins, product name "Omnirad 184") were mixed and irradiated with ultraviolet light under a nitrogen atmosphere to prepare a partial polymer (monomer syrup). 0.2 parts of 1,6-hexanediol diacrylate were added to the obtained monomer syrup and mixed uniformly to prepare a pressure-sensitive adhesive composition C2.
[0149] <Preparation of laminated sheet> (Example 1) The first film has a surface A, which is laminated to the first surface of the adhesive layer, and the surface A is a release surface made of a silicone-based release treatment agent S1. The maximum peak height Rp A1 A PET film (release film) having a thickness of 75 μm and a modulus of elasticity of 26 nm was prepared. The modulus of elasticity of this PET film was calculated from the elastic modulus E′ [MPa] and the thickness T (0.075 mm) of the film, and the modulus of elasticity was calculated as E′×T 3 was 0.99 N·mm. In addition, the second film has a surface A, which is laminated to the second surface of the adhesive layer, as a release surface made of a silicone-based release treatment agent S3, and the maximum peak height Rp A2 A PET film (release film) with a thickness of 75 μm and a T of 23 nm was prepared. 3 was 0.99 N·mm.
[0150] The pressure-sensitive adhesive composition C1 was applied to the A side (release side) of the first film to form a liquid film of the pressure-sensitive adhesive composition C1 on the A side. The amount of the pressure-sensitive adhesive composition applied was adjusted so that the thickness of the finally formed pressure-sensitive adhesive layer was 50 μm. Next, the second film was placed on top of the liquid film so that the A side (release side) of the second film was in contact with the liquid film. This blocked the liquid film from oxygen. With both sides of the liquid film of the pressure-sensitive adhesive composition in contact with the A sides of the first and second films, respectively, a chemical light lamp (manufactured by Toshiba Corporation) was used to illuminate the liquid film at an illuminance of 5 mW / cm. 2 The liquid film was cured by irradiating it with ultraviolet light for 360 seconds to proceed with a polymerization reaction, thereby forming a pressure-sensitive adhesive layer. In this manner, a three-layer laminate sheet was obtained, which was composed of a pressure-sensitive adhesive layer (i.e., a UV-cured product of the liquid film), a first film laminated on a first surface of the pressure-sensitive adhesive layer, and a second film laminated on a second surface of the pressure-sensitive adhesive layer. The above illuminance values are values measured using an industrial UV checker with a peak sensitivity wavelength of about 350 nm (manufactured by Topcon Corporation, product name "UVR-T1", light receiving unit type UD-T36).
[0151] (Example 2) A laminate sheet was obtained in the same manner as in Example 1, except that adhesive composition C2 was used instead of adhesive composition C1.
[0152] (Example 3) The first film has a release surface formed by the long-chain alkyl release agent A1 (the surface of a release treatment layer having a thickness of about 300 nm formed using the release agent A1), and has a thickness and Rp shown in Table 1. A1A PET film having the following properties was prepared. The second film had a release surface formed by the long-chain alkyl release agent A1 (the surface of a release treatment layer having a thickness of about 100 nm formed by using the release agent A1), and had a thickness and Rp shown in Table 1. A2 A laminate sheet was obtained in the same manner as in Example 1 except that these first and second films were used.
[0153] (Example 4) The first film has a release surface made of silicone-based release agent S2 on side A, and the thickness and Rp shown in Table 1 A1 A PET film having the following properties was prepared. The second film had a release surface A made of silicone-based release agent S3, and had a thickness and Rp shown in Table 1. A2 A laminate sheet was obtained in the same manner as in Example 1 except that these first and second films were used.
[0154] (Example 5) The first film has a release surface made of silicone-based release agent S2 on side A, and the thickness and Rp shown in Table 1 A1 A PET film having the following properties was prepared. The second film had a release surface A made of silicone-based release agent S3, and had a thickness and Rp shown in Table 1. A2 A laminate sheet was obtained in the same manner as in Example 1 except that these first and second films were used.
[0155] (Example 6) The first film has a release surface made of silicone-based release agent S1 on side A, and the thickness and Rp shown in Table 1 A1 A PET film having the following properties was prepared. The second film had a release surface A made of silicone-based release agent S2, and had a thickness and Rp shown in Table 1. A2 A laminate sheet was obtained in the same manner as in Example 1 except that these first and second films were used.
[0156] (Example 7) The first film has a release surface made of silicone-based release agent S2 on side A, and the thickness and Rp shown in Table 1 A1 A PET film having the following properties was prepared. The second film had a release surface A made of silicone-based release agent S3, and had a thickness and Rp shown in Table 1. A2 A laminate sheet was obtained in the same manner as in Example 1 except that these first and second films were used.
[0157] (Example 8) The first film has a release surface made of silicone-based release agent S1 on side A, and the thickness and Rp shown in Table 1 A1 A PET film having the following properties was prepared. The second film had a release surface A made of silicone-based release agent S2, and had a thickness and Rp shown in Table 1. A2 A laminate sheet was obtained in the same manner as in Example 1 except that these first and second films were used.
[0158] The silicone-based release agent S1 used was prepared by diluting 100 parts of a silicone-based release agent (KS-847H, manufactured by Shin-Etsu Chemical Co., Ltd.) and 3.3 parts of a silicone curing catalyst (CAT-PL-50T, manufactured by Shin-Etsu Chemical Co., Ltd.) to 0.3% with a mixed solvent of toluene (manufactured by Idemitsu Petrochemical Co., Ltd.), n-hexane (manufactured by Maruzen Petrochemical Co., Ltd.), and methyl ethyl ketone (manufactured by Idemitsu Kosan Co., Ltd.) in a weight ratio of 1:2:1. The silicone-based release treatment agent S2 was prepared by mixing 92 parts of a vinyl group-containing silicone-based release treatment agent (KS-3703, manufactured by Shin-Etsu Chemical Co., Ltd.), 8 parts of a release control agent (KS-3800, manufactured by Shin-Etsu Chemical Co., Ltd.), 3 parts of a platinum catalyst (CAT-PL-50T, manufactured by Shin-Etsu Chemical Co., Ltd.), and 680 parts of toluene and 680 parts of n-hexane as dilution solvents. The silicone-based release treatment agent S3 was prepared by mixing 80 parts of a vinyl group-containing silicone-based release treatment agent (KS-3703, manufactured by Shin-Etsu Chemical Co., Ltd.), 20 parts of a release control agent (KS-3800, manufactured by Shin-Etsu Chemical Co., Ltd.), 3 parts of a platinum catalyst (CAT-PL-50T, manufactured by Shin-Etsu Chemical Co., Ltd.), and 680 parts of toluene and 680 parts of n-hexane as dilution solvents. As the long-chain alkyl-based peeling treatment agent A1, 200 parts of xylene (Taiyo Kagaku, Xylol) and 600 parts of octadecyl isocyanate (Ohara Palladium Chemical, R-NCO) were heated with stirring, and when the xylene began to reflux, 100 parts of polyvinyl alcohol (Kuraray, Kuraray Poval 205) were added in small amounts at 10-minute intervals over 2 hours. After the addition was completed, the mixture was refluxed for another 2 hours. The reaction mixture was then added to methanol to precipitate the reaction product as a white precipitate, which was then filtered off, 140 parts of xylene was added, and the mixture was heated to completely dissolve the reaction product. This was followed by adding methanol again to precipitate the mixture. This procedure was repeated several times, and the precipitate was washed with methanol, dried and pulverized to obtain a powder, which was then diluted with water to 0.3%. The first and second films in Examples 1, 2, and 4 to 8 were prepared by applying the release agent to one side (the surface to be treated) of a PET film as a liner substrate with a bar coater so that the thickness after drying would be 80 nm to 150 nm (for example, about 120 nm), drying at 120° C. for 1 minute, and then aging at 50° C. for 24 hours. The amount of the release agent applied was appropriately adjusted so as to obtain the desired releasability. The first and second films in Example 3 were prepared by applying the release treatment agent to one side (the surface to be treated) of a PET film serving as a liner substrate using a bar coater so that the first film had a thickness of approximately 300 nm after drying, and the second film had a thickness of approximately 100 nm after drying, and then drying the film at 120°C for 1 minute and then aging at 50°C for 24 hours.
[0159] In addition, the maximum peak height Rp of the A side of the first and second films used in each of the above examples is A1 ,Rp A2The measurement was performed in accordance with JIS B 0601:2001 using a stylus type surface roughness measuring instrument "SV3100S4" manufactured by Mitutoyo Corporation. As the cut-off value (reference length), 0.08 mm was used when it was estimated that Ra ≤ 0.02 μm, 0.25 mm was used when it was estimated that 0.02 μm < Ra ≤ 0.1 μm, and 0.8 mm was used when it was estimated that 0.1 μm < Ra ≤ 2 μm, according to the arithmetic mean height Ra estimated for the measurement target surface. The arithmetic mean height Ra estimated for the measurement target surface can be estimated by measuring the arithmetic mean height Ra of the measurement target surface using a non-contact type surface roughness measuring device. As the non-contact type surface roughness measuring device, an optical interference type surface roughness measuring device (for example, Wyko NT-9100 manufactured by Veeco or its equivalent) can be used. As the arithmetic mean height Ra estimated for the A surface of the first and second films used in each of the above examples, the value obtained under the following measurement conditions using Wyko NT-9100 manufactured by Veeco was used. · Measurement area per scan: 622 μm × 467 μm (Objective lens: 10x, FOV (internal lens): 1.0x) · Measurement mode: VSI (Vertical Scan Interferometry) · Back scan: 5 μm · Measurement distance: 10 μm · Threshold value: 0.1% · Scan speed: 1x (Single scan)
[0160] <Measurement of shear peel strength> The obtained laminated sheet was cut to a size of 20 mm wide and 200 mm long, and the release film in contact with the adhesive surface opposite to the release film to be measured was peeled off, and a 50 μm thick PET film was attached to the exposed adhesive surface as a backing material to prepare a sample for shear peel force measurement. At a position 90 mm from one end of the longitudinal direction of the sample, the sample was half-cut from the backing material side so that the backing material and the adhesive layer were cut, and the backing material and the adhesive layer in the range from the one end of the longitudinal direction to 90 mm were peeled off from the release film to be measured. Next, at a position 110 mm from one end of the longitudinal direction of the sample, the sample was half-cut from the release film to be measured so that only the release film to be measured was cut. A tensile test was then carried out using a tensile tester (manufactured by Shimadzu Corporation, device name "Tensilon") at a peel angle of 0 degrees and a tensile speed of 10 mm / min. The maximum peel strength observed until the release film to be measured (cut at a position 110 mm from one end in the longitudinal direction) was peeled off from the adhesive layer was recorded as the shear peel strength [N / 4 cm 2 In an embodiment in which the second film is a supporting substrate, the supporting substrate may be used as the backing material to measure the shear peel strength from the adhesive surface of the first film. In an embodiment in which both the first and second films are release films, if the shear peel strength of the release film in contact with the adhesive surface opposite to the release film to be measured is clearly higher than the shear peel strength of the release film to be measured, the operation of attaching the backing material may be omitted.
[0161] <Preparation of Roll Body> The laminated sheets according to the above examples were produced by using long films each having a width of 1000 mm as the first and second films, and applying the pressure-sensitive adhesive composition to a width of about 930 mm at the center of the width of the first film. Both ends of the width of the laminated sheet according to each example were cut inside the width of the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition to prepare a sample for producing a roll body having a width of 300 mm and a length of about 30 m. A cylindrical core having an outer diameter of 90.2 mm, an inner diameter of 76.2 mm, and an axial length of 305 mm was prepared. One end of the sample in the longitudinal direction (winding start end) was fixed to the outer peripheral surface of the core with a commercially available adhesive tape so that the second film side of each sample for preparing a roll body was on the inner peripheral side, and the remaining part of the sample was wound around the core with a winding tension of about 200 N / m to prepare a roll body. The other end of the sample in the longitudinal direction (winding end end) was fixed to the outer surface of the sample located on the inner peripheral side (side B of the first film) with a commercially available adhesive tape.
[0162] <Optical distortion> The roll body prepared as above was stored in a room at 30°C for 28 days, and then a sample for preparing the roll body located approximately 10 m from the starting end of the winding was cut into a size of 300 mm x 1000 mm to prepare a sample for evaluating optical distortion. This sample (a laminated sheet having a first film / adhesive layer / second film configuration) was held flat and placed between a point light source and a screen, with the second film side of the sample facing the point light source and at an angle of about 45 degrees with respect to the light from the point light source. A xenon lamp C2577 manufactured by Hamamatsu Photonics KK was used as the point light source. The distance from the point light source to the screen was about 100 cm, and the sample was placed at about half that distance. The point light source was turned on, and the image projected onto the screen through the sample was visually observed to evaluate the presence and degree of optical distortion according to the following three levels. The results are shown in Table 1. The evaluation of the optical distortion was performed in an environment of 23°C and 50% RH about 5 minutes after the sample for evaluating optical distortion was taken from the roll after the storage. E: No optical distortion is observed G: Some optical distortion is observed, but is within the range of acceptable practical use. P: Obvious optical distortion is observed.
[0163] <Surface smoothness> In evaluating the optical distortion, the first film was peeled off from the sample to expose the adhesive surface, and the exposed adhesive surface and the image projected onto the screen were visually observed to evaluate the smoothness of the surface of the adhesive layer (first adhesive surface) according to the following three levels. E: No citron peel was observed, and the surface was smooth (excellent surface smoothness). G: A slight amount of citron peel was observed, but it was within the range acceptable for practical use. P: The appearance of yuzu skin is observed (poor surface smoothness).
[0164] [Table 1]
[0165] As shown in Table 1, Rp 1A is less than 50 nm, and the total thickness T SUM The laminate sheets of Examples 1 to 5, in which the Rp was 80 μm or more, had high surface smoothness and little optical distortion, and therefore had good optical homogeneity. 1A In Examples 1 to 3, where Rp was 30 nm or less, particularly high surface smoothness was obtained. 1A In Examples 6 and 8, where T is large, sufficient surface smoothness cannot be obtained. SUM In Examples 6 and 7, where Rp is less than 80 μm, 1A The occurrence of optical distortion was observed regardless of the value of
[0166] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]
[0167] 10 Adhesive layer 10a First side (first adhesive side) 10b Second side (second adhesive side) 21 First film (release film) 21a A side (peeling surface) 21b Side B 22 Second film (release film) 22a A side (peeling surface) 22b Side B 32 Second film (support substrate) 32a A side (non-peeling side) 32b B side 40,50 Laminated sheet 42,52 Adhesive sheet 80 cores 100,200 rolls
Claims
1. A pressure-sensitive adhesive layer, a first film laminated on a first surface of the pressure-sensitive adhesive layer, and a second film laminated on a second surface of the pressure-sensitive adhesive layer, the first film is a release film having a release surface on side A, which is the surface in contact with the pressure-sensitive adhesive layer, and having a release treatment layer that forms the release surface on the surface of a release film substrate; The first film has a maximum peak height Rp 1A is less than 50 nm, the second film is a release film having a release surface on side A, which is the surface in contact with the pressure-sensitive adhesive layer, and having a release treatment layer that forms the release surface of the second film on a surface of a release film substrate; The second film has a maximum peak height Rp 2A is less than 50 nm, The total thickness T of the first film and the second film SUM is 80 μm or more, the first film and the second film each have a thickness of 35 μm or more, and at least one of the first film and the second film has a thickness of 50 μm or more; The first film and the second film have a thickness T [mm] and an elastic modulus E′ [MPa], where E′×T 3 and at least one of the first film and the second film has a value of E′×T 3 The laminate sheet has a value of 0.20 N mm or more.
2. The laminate sheet according to claim 1 , wherein the pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer formed from a photocurable pressure-sensitive adhesive composition.
3. Shear peel strength Fs of the A side of the first film to the first side of the pressure-sensitive adhesive layer 1 0.5N / 4cm 2 More than 250N / 4cm 2 3. The laminate sheet according to claim 1 or 2, wherein:
4. The laminate sheet according to any one of claims 1 to 3, wherein the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is an acrylic pressure-sensitive adhesive.
5. The laminate sheet according to any one of claims 1 to 4, which is used for producing an optical member having the pressure-sensitive adhesive layer.
Citation Information
Patent Citations
Portable electronic equipment
JP1988000788A
Double coated pressure-sensitive adhesive sheet and method for fixing plastic film
JP2009215522A
Double-sided tacky sheet and coiled body
JP2014189778A
Mold release film, method for producing green sheet and method for producing multilayer ceramic electronic component
JP2015134476A
Protective sheet
JP2018172611A